A method for preparing porous carbon material by microwave-assisted extraction of biomass lignin and its application

Through microwave-assisted extraction of biomass lignin and high-temperature carbonization and pyrolysis activation processes, porous carbon materials with graded porous structures were prepared, which solved the problem of poor rate performance of existing porous carbon materials and significantly improved the electrochemical performance.

CN119409191BActive Publication Date: 2025-04-11NANJING YUANHUA NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510019760.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The current porous carbon materials have poor rate performance of supercapacitors under high current density, mainly due to the long ion transmission channels and high ion transmission resistance, resulting in low micropore utilization.

Method used

Microwave-assisted extraction of biomass lignin is used to prepare porous carbon materials with a graded porous structure through high-temperature carbonization and pyrolysis activation processes. The material consists of a carbon shell skeleton and a nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell skeleton. It has both micropores, mesopores and macropores, shortening the diffusion path of electrolyte ions and enhancing its permeability and transmission efficiency.

Benefits of technology

The electrochemical performance of porous carbon materials is significantly improved, including specific capacitance and rate performance, and meets the requirements of supercapacitors for excellent capacitance and high rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409191B_ABST
    Figure CN119409191B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery materials, and relates to a method for preparing a porous carbon material by microwave-assisted extraction of biomass lignin and an application thereof. The porous carbon material prepared by the present invention consists of a carbon shell skeleton and nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell skeleton. The porous carbon material has micropores, mesopores and macropores. The graded porous structure can greatly shorten the diffusion path of electrolyte ions in the pores, effectively enhance the permeability of the electrolyte to the internal surface of the porous carbon material, and provide a short and low-resistance ion diffusion channel, which is beneficial to the transmission of electrolyte ions in the porous carbon material, and meets the requirements of supercapacitors for excellent capacitance performance and high rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin and application thereof. Background Art

[0002] According to the different energy storage mechanisms, supercapacitors can be divided into two types, namely: double-layer capacitors and pseudocapacitors. Double-layer capacitors are based on the accumulation of static electricity at the interface between electrodes and electrolytes for energy storage. Commonly used electrode materials include carbon-based porous materials such as activated carbon, carbon nanotubes, and carbon aerogels. It is worth noting that the charging and discharging process of double-layer capacitors mainly occurs on the surface of the electrode material, so the electrochemical performance of the capacitor depends largely on the specific surface area of ​​the electrode material.

[0003] Lignin is a natural, renewable, aromatic-ring-rich polymer that is widely found in the xylem of plants, with an annual production of 150 billion tons worldwide. Lignin has a carbon content of 50-60%, and is an excellent precursor for the preparation of carbon materials. Compared with the commonly used carbon sources such as glucose, sucrose, phenolic resin, and carbon nanomaterials, the use of lignin as a carbon source not only has the advantages of a wide source and low cost, but also can turn waste into treasure, which is beneficial to environmental protection and resource utilization.

[0004] Porous carbon materials have a large specific surface area and low cost, making them one of the more commonly used double-layer capacitor electrode materials.

[0005] CN116588931A discloses a method for preparing lignin-based hierarchical porous carbon with small molecular lignin as a porogen. Based on the polydispersity of lignin molecular weight, the small molecular lignin fraction is separated by solvent dissolution, and then a porous macromolecular lignin solid insoluble is obtained, which is then carbonized by an activator under high temperature conditions, washed and dried to obtain lignin-based hierarchical porous carbon with small molecular lignin as a porogen. However, the hierarchical pore structure of the porous carbon material prepared by this technology is not obvious, and the rate performance of the capacitor is poor at high current density.

[0006] CN108751160A discloses a lignin porous carbon with uniform pores, a preparation method thereof and an application of the lignin porous carbon in a negative electrode material for a lithium ion battery. The preparation method comprises the following steps: mixing alkaline lignin and a co-solvent and then dissolving them in ethanol to prepare an ethanol solution with a concentration of 5-20 g / L, adding nano silicon dioxide, adding water to precipitate, separating the precipitate, and drying to obtain a silicon dioxide / lignin mixture; adding the mixture in water with a pH value of 2-4 to prepare a suspension with a concentration of 10-100 g / L, reacting at 120-200° C. for 1-3 hours, filtering, drying, placing the mixture in an inert atmosphere, and carbonizing the mixture at 500-900° C. for 2-5 hours to obtain a silicon dioxide / lignin carbon composite material; immersing the mixture in a 1-5 mol / L alkali solution and stirring the mixture for 1-24 hours, and then washing the mixture with water, filtering, and drying the mixture to obtain a lignin porous carbon material with uniform pores. However, the porous carbon materials prepared by this technology also have the problem of low micropore utilization and long ion diffusion channels, which affects the capacitance and rate performance of the porous carbon materials.

[0007] In summary, the existing porous carbon materials have long ion transmission channels and high ion transmission resistance, resulting in low micropore utilization of porous carbon materials and poor rate performance of supercapacitors at high current density, which will seriously affect their application in high-power energy storage devices. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin and its application. The porous carbon material prepared by the present invention consists of a carbon shell skeleton and nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell skeleton. It has micropores, mesopores and macropores. The graded porous structure can greatly shorten the diffusion path of electrolyte ions in the pores, effectively enhance the permeability of electrolyte to the internal surface of the porous carbon material, and provide a short and low-resistance ion diffusion channel, which is beneficial to the transmission of electrolyte ions in the porous carbon material, and meets the requirements of supercapacitors for excellent capacitance performance and high rate performance.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a porous carbon material by microwave-assisted extraction of biomass lignin, the method comprising:

[0011] (I) dispersing lignin in deionized water to obtain a lignin solution, dropping an acetic acid solution into the lignin solution to adjust the pH value thereof, then sequentially adding chitosan and sodium dihydrogen phosphate into the lignin solution, mixing and stirring to obtain a precursor solution; adding halloysite to the precursor solution to obtain a suspension, placing the suspension in a negative pressure environment and then centrifuging at high speed, washing and freeze-drying the precipitate after centrifugation to obtain a porous carbon precursor;

[0012] (II) dissolving hexadecyltrimethylammonium bromide in anhydrous ethanol to obtain a dispersed solution, adding an ammonia solution and the porous carbon precursor obtained in step (I) to the dispersed solution, mixing, stirring and ultrasonically dispersing to obtain a reaction precursor solution; preparing a hydrolyzate containing tetraethyl orthosilicate, adding the reaction precursor solution to the hydrolyzate while stirring to obtain a composite precursor sol, allowing the composite precursor sol to stand and age under a constant temperature environment to obtain a composite precursor gel; freeze-drying the composite precursor gel to obtain a composite porous carbon precursor, wherein the composite porous carbon precursor is composed of the porous carbon precursor and nano-silicon dioxide coated on the surface thereof;

[0013] (III) adding organic template microspheres to a dopamine solution, mixing and stirring, and then standing to form a polydopamine coating layer on the surface of the organic template microspheres to obtain a template solution; then, adding the composite porous carbon precursor obtained in step (II) to the template solution, mixing and stirring, and then standing to allow the composite porous carbon precursor to be loaded on the surface of the polydopamine coating layer to obtain a reaction solution, filtering, washing and drying the reaction solution to obtain composite precursor particles; high-temperature carbonizing the composite precursor particles to obtain a composite carbide; then, immersing the composite carbide in a hydrofluoric acid solution, filtering, washing and drying to obtain a primary porous carbon material, wherein the primary porous carbon material is composed of a carbon shell and nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell;

[0014] (IV) Evenly mixing the primary porous carbon material obtained in step (III) with potassium carbonate and grinding them thoroughly to obtain an activated mixture; spreading the activated mixture evenly in a porcelain boat, placing the porcelain boat in a horizontal tube furnace, and pyrolyzing and activating the activated mixture under a nitrogen atmosphere to obtain an activated product, and washing the activated product to obtain the porous carbon material.

[0015] Biomass mainly contains three components: cellulose, hemicellulose and lignin. When the temperature is higher than 500°C, cellulose and hemicellulose will volatilize into gas and form a small amount of carbon. Lignin has aromatic properties and decomposes slowly when heated, so it is the main material for forming carbon. The present invention uses microwave and ultrasound to jointly assist in extracting lignin from biomass, and uses nitrogen-phosphorus co-doped lignin as the microsphere carbon source, and uses halloysite and nano-silica as the microsphere hard templates. Nitrogen-phosphorus co-doped porous carbon microspheres are formed after high-temperature carbonization and pyrolysis activation. Polydopamine is used as the carbon shell skeleton carbon source, and organic template microspheres are used as the carbon shell hard template. After high-temperature carbonization and pyrolysis activation, a carbon shell skeleton is formed, and finally a porous carbon material with a hierarchical porous structure is prepared. The porous carbon material prepared by the present invention is composed of a carbon shell skeleton and nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell skeleton. It has micropores, mesopores and macropores. The hierarchical porous structure can greatly shorten the diffusion path of electrolyte ions in the pores, effectively enhance the permeability of the electrolyte to the internal surface of the porous carbon material, and provide a short and low-resistance ion diffusion channel, which is beneficial to the transmission of electrolyte ions in the porous carbon material, and meets the requirements of supercapacitors for excellent capacitance performance and high rate performance.

[0016] The present invention adopts a two-stage calcination process of high-temperature carbonization and pyrolysis activation to prepare a porous carbon material. First, by high-temperature carbonization, the moisture and most of the volatiles in the raw material are removed to obtain a primary porous carbon material containing a stable carbon content. Subsequently, the primary porous carbon material is evenly mixed with a potassium carbonate activator and then pyrolyzed and activated. While removing the remaining small amount of volatiles, the potassium carbonate activator and the primary porous carbon material undergo a chemical reaction at high temperature, and holes are etched on the surface of the primary porous carbon material to further enrich the pore structure of the porous carbon material and provide more ion transmission channels, allowing a large number of electrolyte ions to quickly reach the electrode / electrolyte interface to complete charge storage. Therefore, the porous carbon material prepared by the present invention can show obvious electrochemical advantages when used in the battery material of a supercapacitor.

[0017] The porous carbon material prepared by the present invention has a micropore structure of 1-3 nm, an ordered mesopore structure of 5-10 nm and a macropore structure of 20-30 nm. The three-dimensional interconnected conductive network formed by the combination of micropores, ordered mesopores and macropores enables the porous carbon material to show the advantages of different pore sizes and have a synergistic effect during the electrochemical charge-discharge process.

[0018] The microporous structure mainly exists on the surface of the carbon shell skeleton formed by the high-temperature carbonization of the polydopamine layer. The organic template microspheres are cracked during the high-temperature carbonization process to generate gases such as carbon dioxide and water vapor. The cracked gases form a microporous structure on the surface of the carbon shell skeleton during the process of escaping the carbon shell skeleton. Based on the energy storage mechanism of double-layer capacitance, the charge accumulates at the interface between the electrolyte and the electrode material. Therefore, the specific surface area of ​​the porous carbon material will be conducive to improving the specific capacitance of the porous carbon material. The number of micropores plays a decisive role in the specific surface area of ​​the porous carbon material. The microporous structure can not only provide adsorption sites to improve the selectivity, but also significantly increase the specific surface area of ​​the porous carbon material, thereby improving the double-layer capacitance. However, the pore size of the microporous structure is small, which is not conducive to the transmission of electrolyte ions in the pores. The ordered mesoporous structure can serve as an ion transmission channel, thereby making up for the shortcomings of the microporous structure. The mesoporous structure provides an effective ion transmission path and a larger pore volume, accelerates the kinetic process of ion migration, and can effectively reduce the transmission resistance of electrolyte ions from the electrolyte to the inner pore surface of the porous carbon microspheres.

[0019] The ordered mesoporous structure mainly exists on the surface and inside of the porous carbon microspheres. The present invention uses halloysite with a developed pore structure with a tubular inner cavity as the main template, nano-silica particles as the secondary template, and nitrogen-phosphorus co-doped lignin as the microsphere carbon source. Porous carbon microspheres with abundant ordered mesoporous channels are prepared by high-temperature carbonization and hydrofluoric acid pickling.

[0020] The mechanism of action of the halloysite main template is as follows: when the high-temperature carbonization temperature reaches 400°C, halloysite will undergo dehydration, and there will be hydrogen bonding between the hydroxyl functional groups on the surface of halloysite. Under the action of dehydration and hydrogen bonding, halloysite will agglomerate to form a halloysite microsphere template with a developed pore structure composed of halloysite nanotubes. There are also a large number of open micropores near the pore walls of the pore structure. Under the skeletal support of the halloysite microsphere template, the porous carbon microspheres formed by lignin during the high-temperature carbonization process are not easy to collapse. By using the microsphere template with a developed pore structure, porous carbon microspheres with a developed pore structure corresponding to its structure can be obtained. After the high-temperature carbonization is completed, the halloysite microsphere template in the composite carbide is removed by a hydrofluoric acid solution, and finally porous carbon microspheres are obtained, thereby forming abundant ordered mesoporous channels inside the porous carbon microspheres and open micropores located at the pore walls of the ordered mesoporous channels.

[0021] The mechanism of action of the nano-silica particle sub-template is as follows: under the action of the surfactant hexadecyltrimethylammonium bromide, ethyl orthosilicate is hydrolyzed on the surface of the porous carbon precursor to form nano-silica particles, and the nano-silica particles are uniformly attached to the surface of the porous carbon precursor. The nano-silica particles on the surface of the composite carbide can be removed in the subsequent hydrofluoric acid solution pickling process, thereby forming pits on the surface of the porous carbon microspheres formed after the high-temperature carbonization of the porous carbon precursor, which can not only serve as ion buffer-storage containers, but also realize the opening of the ordered mesoporous channels inside the porous carbon microspheres, so that the ordered mesoporous channels inside the porous carbon microspheres are connected with the surface of the porous carbon microspheres, and the electrolyte ions can enter the ordered mesoporous channels inside the porous carbon microspheres more quickly from the surface of the porous carbon microspheres.

[0022] The macroporous structure is composed of gaps formed by the accumulation of porous carbon microspheres supported on the surface of the carbon shell skeleton. The macroporous structure can be used as an ion buffer-storage container to minimize the diffusion distance of electrolyte ions, which can improve the power performance of porous carbon materials at high current density.

[0023] The transport movement path of electrolyte ions in the porous carbon material prepared by the present invention is: the macroporous structure formed by the stacking gap of the porous carbon microspheres mainly acts as an ion buffer area, and the electrolyte ions can enter the ordered mesoporous ion diffusion channel inside the porous carbon microspheres. The ion diffusion channel ensures that the electrolyte ions have a shorter diffusion path and diffusion time in different directions, and can achieve rapid diffusion of electrolyte ions, thereby obtaining excellent rate performance; at the same time, under the action of the halloysite main template and the nano-silica sub-template, the interior of the porous carbon microspheres, in addition to the ion diffusion channel with a mesoporous structure, will also form a large number of open micropores with good wettability near the pore wall of the ion diffusion channel, which is conducive to the storage and transmission of electrolyte ions. Subsequently, the electrolyte ions quickly diffuse into the open microporous structure on the carbon shell skeleton along the ion diffusion channel, and enter the interior of the carbon shell skeleton through the microporous structure.

[0024] The present invention coats the surface of the organic template microsphere with a polydopamine layer, and a closed pyrolysis space can be formed on the surface of the organic template microsphere. The organic template microsphere acts as a carbon shell skeleton template of porous carbon during the pyrolysis process of the pyrolysis space. The polydopamine layer coated on the surface of the organic template microsphere is carbonized at high temperature. At the same time, the organic template microsphere decomposes at high temperature, thereby forming a spherical carbon shell skeleton with a hollow structure. During the pyrolysis process of the organic template microsphere, pyrolysis gases such as carbon dioxide and water vapor are generated, but due to the coating of the polydopamine layer, a closed space is formed on the outer surface of the organic template microsphere, resulting in the pyrolysis gas being unable to escape quickly. As the pyrolysis process continues, the amount of pyrolysis gas generated gradually increases, and the internal pressure of the closed space gradually increases. When the internal pressure of the closed space reaches a certain level, the pyrolysis gas will break through the carbon shell and escape. As the pyrolysis gas escapes, a rich microporous structure is formed on the surface of the carbon shell skeleton.

[0025] In order to further improve the energy density and power output of porous carbon materials, the present invention uses chitosan as a nitrogen source and sodium dihydrogen phosphate as a phosphorus source to co-dope porous carbon microspheres with nitrogen and phosphorus. The skeleton structure of the porous carbon microspheres can be changed by doping with nitrogen and phosphorus heteroatoms, which not only expands the interlayer spacing of the porous carbon microsphere structure, improves the hydrophilicity of the porous carbon material, and improves the wettability of the porous carbon material, but also generates a large number of defects and reaction active sites for storing electrolyte ions, enhances the diffusion ability of electrolyte ions in the porous carbon material, ensures that the electrolyte ions can efficiently utilize the higher surface area and larger pore volume of the porous carbon material, thereby reducing the loss of specific capacitance and improving the rate performance of the porous carbon material.

[0026] Doping nitrogen atoms in the porous carbon microsphere skeleton will significantly improve the surface charge state of the carbon matrix and improve the conductivity of the porous carbon microspheres; at the same time, the rich nitrogen-containing functional groups can significantly improve the wettability of the porous carbon material in the electrolyte. In addition, the atomic radius of phosphorus is larger than that of nitrogen. Doping phosphorus atoms in the porous carbon microspheres will further expand the interlayer spacing of the porous carbon microspheres, and the specific surface area of ​​the porous carbon material can be fully utilized by the electrolyte ions to store more charge and improve its specific capacitance. In addition, phosphorus atoms can connect unstable functional groups to the porous carbon microspheres, enhancing the stability of the porous carbon material. Using sodium dihydrogen phosphate as a phosphorus source can not only provide phosphorus atom doping, but also the water vapor and sodium ions generated when it is heated and decomposed can also be used as activators to form pores. When activated by potassium carbonate, alkali metal potassium is formed and etched on the unexposed surface. After acid washing, the potassium ions in the porous carbon microspheres are removed, and a large number of vacancies appear, thereby giving the porous carbon microspheres a certain number of microporous structures. More micropores are conducive to storing charges and can improve the electrochemical properties of porous carbon materials.

[0027] The present invention uses potassium carbonate to perform pyrolysis activation on the primary porous carbon material, which can greatly increase the specific surface area of ​​the porous carbon material, facilitate the contact area and accelerated transmission between the porous carbon material and the electrolyte ions, and improve the ability of the porous carbon material to store charge. During the pyrolysis activation process, potassium carbonate will decompose into K2O and CO2, and K2O and CO2 will further react with carbon to form potassium vapor and carbon monoxide, respectively. Potassium vapor and carbon monoxide are inserted into the carbon matrix to form a richer pore structure. The reaction principle of this process is as follows:

[0028] K2CO3→K2O+CO2

[0029] CO2+C→2CO

[0030] K2O+C→2K+CO

[0031] Using potassium carbonate as an activator in combination with the nitrogen doping agent chitosan, porous carbon microspheres with high surface area and nitrogen content can be formed. Chitosan can form a complex with potassium carbonate to generate KCNO during the pyrolysis activation process. As the pyrolysis activation temperature continues to increase, the carbon matrix can also reduce KCNO, and the reaction equation is: KCNO+C→KCN+CO. The carbon monoxide gas generated by the carbon thermal reduction reaction can be used as a pore-forming agent to promote the pore formation of porous carbon microspheres.

[0032] As a preferred technical solution of the present invention, in step (I), the lignin is prepared by the following method:

[0033] The biomass raw material is crushed, sieved and frozen with liquid nitrogen in sequence to obtain biomass powder; the biomass powder is dispersed in an ethanol aqueous solution to form a biomass dispersion liquid, the biomass dispersion liquid is preheated by microwave, and then the biomass dispersion liquid is simultaneously subjected to ultrasonic treatment and microwave treatment, and after the treatment, it is extracted and filtered, a hydrochloric acid solution is added to the filtrate to adjust its pH value, and after centrifugal separation, the precipitate is taken out and dried to obtain lignin.

[0034] In some optional examples, the biomass raw material includes any one of corn straw, rice straw, wheat straw, wood chips, sawdust, fruit shells or fruit cores, or a combination of at least two of them.

[0035] In some optional embodiments, the mesh size of the sieve used for screening is 100-200 mesh, for example, it can be 100 mesh, 110 mesh, 120 mesh, 130 mesh, 140 mesh, 150 mesh, 160 mesh, 170 mesh, 180 mesh, 190 mesh or 200 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In some optional examples, the liquid nitrogen freezing operation process is: immersing the sieved raw material powder in liquid nitrogen, taking it out after immersion for a period of time, immersing it in liquid nitrogen again, and repeating it multiple times.

[0037] In some optional examples, the raw material powder is immersed in liquid nitrogen for 3 to 5 minutes each time, for example, it can be 3.0 minutes, 3.2 minutes, 3.4 minutes, 3.6 minutes, 3.8 minutes, 4.0 minutes, 4.2 minutes, 4.4 minutes, 4.6 minutes, 4.8 minutes or 5.0 minutes; the raw material powder is immersed in liquid nitrogen for 5 to 8 times, for example, it can be 5 times, 6 times, 7 times or 8 times, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] In some optional examples, the mass ratio of the biomass powder to the ethanol aqueous solution is (0.1~0.3):1, for example, it can be 0.1:1, 0.12:1, 0.14:1, 0.16:1, 0.18:1, 0.2:1, 0.22:1, 0.24:1, 0.26:1, 0.28:1 or 0.3:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In some optional examples, the volume fraction of ethanol in the ethanol aqueous solution is 30-40%, for example, it can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or 40%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In some optional examples, the microwave power of the microwave preheating of the biomass dispersion is 700~800W, for example, it can be 700W, 710W, 720W, 730W, 740W, 750W, 760W, 770W, 780W, 790W or 800W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] In some optional examples, the microwave frequency of the microwave preheating of the biomass dispersion is 500-600 MHz, for example, it can be 500 MHz, 510 MHz, 520 MHz, 530 MHz, 540 MHz, 550 MHz, 560 MHz, 570 MHz, 580 MHz, 590 MHz or 600 MHz, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In some optional examples, the microwave preheating treatment time of the biomass dispersion is 5 to 8 min, for example, it can be 5.0 min, 5.2 min, 5.4 min, 5.6 min, 5.8 min, 6.0 min, 6.2 min, 6.4 min, 6.6 min, 6.8 min, 7.0 min, 7.2 min, 7.4 min, 7.6 min, 7.8 min or 8.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In some optional examples, the ultrasonic power of the ultrasonic treatment of the biomass dispersion is 1000~2000W, for example, it can be 1000W, 1100W, 1200W, 1300W, 1400W, 1500W, 1600W, 1700W, 1800W, 1900W or 2000W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In some optional examples, the ultrasonic frequency of the ultrasonic treatment of the biomass dispersion is 0.5~1.5 MHz, for example, it can be 0.5 MHz, 0.6 MHz, 0.7 MHz, 0.8 MHz, 0.9 MHz, 1.0 MHz, 1.1 MHz, 1.2 MHz, 1.3 MHz, 1.4 MHz or 1.5 MHz, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] In some optional examples, the microwave power of the microwave treatment of the biomass dispersion is 2000~3000W, for example, it can be 2000W, 2100W, 2200W, 2300W, 2400W, 2500W, 2600W, 2700W, 2800W, 2900W or 3000W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In some optional examples, the microwave frequency of the microwave treatment of the biomass dispersion is 1000~1500 MHz, for example, it can be 1000 MHz, 1050 MHz, 1100 MHz, 1150 MHz, 1200 MHz, 1250 MHz, 1300 MHz, 1350 MHz, 1400 MHz, 1450 MHz or 1500 MHz, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In some optional examples, the treatment time of the ultrasonic treatment and microwave treatment of the biomass dispersion is 10 to 20 minutes, for example, it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In some optional examples, the extraction time is 50 to 60 min, for example, it can be 50 min, 51 min, 52 min, 53 min, 54 min, 55 min, 56 min, 57 min, 58 min, 59 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] In some optional examples, the extraction temperature is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional examples, the solid-liquid ratio of the extraction is 1g:(10~20)mL, for example, it can be 1g:10mL, 1g:11mL, 1g:12mL, 1g:13mL, 1g:14mL, 1g:15mL, 1g:16mL, 1g:17mL, 1g:18mL, 1g:19mL or 1g:20mL, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In some optional examples, the organic solvent used for the leaching is any one of ethylene glycol, 1,4-butanediol, acetone or methanol, or a combination of at least two of them.

[0052] In some optional examples, the concentration of the hydrochloric acid solution is 1.5~2.5 mol / L, for example, it can be 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L or 2.5 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In some optional examples, hydrochloric acid solution is added to the filtrate to adjust the pH value of the filtrate to 3-5, for example, it can be 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8 or 5.0, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] As a preferred technical solution of the present invention, in step (I), the mass ratio of the lignin to the deionized water is 1:(20-30), for example, it can be 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In some optional examples, the mass fraction of the acetic acid solution is 8~12wt%, for example, it can be 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt%, 10.0wt%, 10.5wt%, 11.0wt%, 11.5wt% or 12.0wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In some optional examples, acetic acid solution is added dropwise to the lignin solution to adjust the pH value of the lignin solution to 5-6, for example, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9 or 6.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In some optional examples, the mass ratio of the lignin in the lignin solution, the chitosan and the sodium dihydrogen phosphate is 1:(0.4~0.5):(0.6~0.7), for example, it can be 1:0.4:0.6, 1:0.41:0.61, 1:0.42:0.62, 1:0.43:0.63, 1:0.44:0.64, 1:0.45:0.65, 1:0.46:0.66, 1:0.47:0.67, 1:0.48:0.68, 1:0.49:0.69 or 1:0.5:0.7, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] As a preferred technical solution of the present invention, in step (I), the mass ratio of the halloysite to the lignin in the precursor solution is 1:(1.2~1.4), for example, it can be 1:1.2, 1:1.22, 1:1.24, 1:1.26, 1:1.28, 1:1.3, 1:1.32, 1:1.34, 1:1.36, 1:1.38 or 1:1.4, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] The present invention specifically limits the mass ratio of halloysite to lignin in the precursor solution to 1:(1.2~1.4). When the addition amount of lignin is too high, part of the mesoporous channels in the porous carbon microspheres will be blocked, thereby disrupting the orderliness of the mesoporous distribution inside the porous carbon microspheres, making the transmission path of electrolyte ions in the mesoporous channels more tortuous and the transmission resistance larger, which will lead to an increase in the internal resistance of the porous carbon material and a decrease in the specific capacitance of the porous carbon material.

[0060] In some optional examples, after adding halloysite to the precursor solution, ultrasonic dispersion is carried out to obtain the suspension, wherein the ultrasonic power of the ultrasonic dispersion is 200~300W, for example, it can be 200W, 210W, 220W, 230W, 240W, 250W, 260W, 270W, 280W, 290W or 300W; the ultrasonic time of the ultrasonic dispersion is 30~40min, for example, it can be 30min, 31min, 32min, 33min, 34min, 35min, 36min, 37min, 38min, 39min or 40min, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] In some optional instances, the pressure of the negative pressure environment is -0.5~-0.7MPa, for example, it can be -0.5MPa, -0.52MPa, -0.54MPa, -0.56MPa, -0.58MPa, -0.6MPa, -0.62MPa, -0.64MPa, -0.66MPa, -0.68MPa or -0.7MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In some optional examples, the suspension is allowed to stand in the negative pressure environment for 1.5 to 2.5 hours, for example, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours or 2.5 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] In some optional examples, the rotation speed of the high-speed centrifugation is 2000~3000r / min, for example, it can be 2000r / min, 2100r / min, 2200r / min, 2300r / min, 2400r / min, 2500r / min, 2600r / min, 2700r / min, 2800r / min, 2900r / min or 3000r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] In some optional examples, the high-speed centrifugation time is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] In some optional embodiments, the freeze-drying temperature is -40~-50°C, for example, it can be -40°C, -41°C, -42°C, -43°C, -44°C, -45°C, -46°C, -47°C, -48°C, -49°C or -50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] In some optional embodiments, the freeze-drying time is 24 to 36 hours, for example, it can be 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours or 46 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] As a preferred technical solution of the present invention, in step (II), the mass fraction of hexadecyltrimethylammonium bromide in the dispersed solution is 3-5wt%, for example, it can be 3.0wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt%, 4.0wt%, 4.2wt%, 4.4wt%, 4.6wt%, 4.8wt% or 5.0wt%, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0068] In some optional examples, the ratio of hexadecyltrimethylammonium bromide, the ammonia solution and the porous carbon precursor in the dispersed solution is (5~6)g:(30~50)mL:1g, for example, it can be 5g:30mL:1g, 5.1g:32mL:1g, 5.2g:34mL:1g, 5.3g:36mL:1g, 5.4g:38mL:1g, 5.5g:40mL:1g, 5.6g:42mL:1g, 5.7g:44mL:1g, 5.8g:46mL:1g, 5.9g:48mL:1g, 6g:50mL:1g, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0069] In some optional examples, the concentration of the aqueous ammonia solution is 22~25wt%, for example, it can be 22wt%, 22.2wt%, 22.4wt%, 22.6wt%, 22.8wt%, 23wt%, 23.2wt%, 23.4wt%, 23.6wt%, 23.8wt%, 24wt%, 24.2wt%, 24.6wt%, 24.8wt% or 25wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] In some optional examples, the ultrasonic power after adding ammonia solution and porous carbon precursor to the dispersed solution is 400~500W, for example, it can be 400W, 410W, 420W, 430W, 440W, 450W, 460W, 470W, 480W, 490W or 500W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] In some optional examples, the ultrasonic time after adding the ammonia solution and the porous carbon precursor to the dispersed solution is 20 to 30 minutes, for example, it can be 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes or 30 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] In some optional examples, the hydrolyzate containing ethyl orthosilicate is prepared by the following method:

[0073] Mixing and stirring tetraethyl orthosilicate, ethanol and deionized water to obtain a tetraethyl orthosilicate solution, adding a nitric acid solution dropwise to the tetraethyl orthosilicate solution to adjust the pH value thereof, and then stirring the tetraethyl orthosilicate solution to obtain a hydrolyzate;

[0074] In some optional examples, the volume ratio of the tetraethyl orthosilicate, ethanol and deionized water is 1:(1.6~1.7):(0.2~0.3), for example, it can be 1:1.6:0.2, 1:1.61:0.21, 1:1.62:0.22, 1:1.63:0.23, 1:1.64:0.24, 1:1.65:0.25, 1:1.66:0.26, 1:1.67:0.27, 1:1.68:0.28, 1:1.69:0.29 or 1:1.7:0.3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0075] In some optional instances, the concentration of the nitric acid solution is 1~2 mol / L, for example, it can be 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2.0 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0076] In some optional examples, a nitric acid solution is added dropwise to the tetraethyl orthosilicate solution to adjust the pH value of the tetraethyl orthosilicate solution to 4-5, for example, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9 or 5.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0077] In some optional examples, the stirring time of the ethyl orthosilicate solution is 5 to 6 hours, for example, it can be 5.0 hours, 5.1 hours, 5.2 hours, 5.3 hours, 5.4 hours, 5.5 hours, 5.6 hours, 5.7 hours, 5.8 hours, 5.9 hours or 6.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0078] As a preferred technical solution of the present invention, in step (II), the hydrolyzate and the reaction precursor solution are mixed according to a volume ratio of the tetraethyl orthosilicate to the ammonia solution of 1:(3-5), for example, it can be 1:3.0, 1:3.2, 1:3.4, 1:3.6, 1:3.8, 1:4.0, 1:4.2, 1:4.4, 1:4.6, 1:4.8 or 1:5.0, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0079] In some optional instances, the temperature of the constant temperature environment is 40-45°C, for example, it may be 40°C, 40.5°C, 41°C, 41.5°C, 42°C, 42.5°C, 43°C, 43.5°C, 44°C, 44.5°C or 45°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0080] In some optional examples, the composite precursor sol is allowed to stand for 3 to 5 hours in a constant temperature environment, for example, 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0081] In some optional examples, the freeze-drying temperature of the composite precursor gel is -40~-50°C, for example, it can be -40°C, -41°C, -42°C, -43°C, -44°C, -45°C, -46°C, -47°C, -48°C, -49°C or -50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0082] In some optional examples, the freeze-drying time of the composite precursor gel is 24 to 36 hours, for example, it can be 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours or 46 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0083] As a preferred technical solution of the present invention, in step (III), the dopamine solution is prepared by the following method:

[0084] Dopamine was dissolved in Tris-HCl buffer to obtain a dopamine solution.

[0085] In some optional examples, the concentration of dopamine in the dopamine solution is 5-8 g / L, for example, it can be 5.0 g / L, 5.2 g / L, 5.4 g / L, 5.6 g / L, 5.8 g / L, 6.0 g / L, 6.2 g / L, 6.4 g / L, 6.6 g / L, 6.8 g / L, 7.0 g / L, 7.2 g / L, 7.4 g / L, 7.6 g / L, 7.8 g / L or 8.0 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0086] In some optional embodiments, the pH value of the dopamine solution is 8-9, for example, it can be 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0087] In some optional examples, the particle size of the organic template microspheres is 4 to 5 μm, for example, it can be 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm or 5.0 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] In some optional examples, the material of the organic template microspheres is polystyrene.

[0089] In some optional examples, the mass ratio of the organic template microspheres to dopamine in the dopamine solution is 1:(4~5), for example, it can be 1:4.0, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] The present invention particularly limits the mass ratio of the organic template microspheres to the dopamine in the dopamine solution to 1:(4-5). When the amount of dopamine added is lower than the lower limit of the range defined by the present invention, too little dopamine is deposited on the surface of the organic template microspheres, the thickness of the formed polydopamine layer is relatively thin, and the structure is unstable. In the subsequent high-temperature carbonization process, the polydopamine layer is prone to collapse and cannot form a carbon shell skeleton with a complete shape, thereby affecting the formation of micropores. At the same time, if the carbon shell skeleton is too thin, it is not conducive to the attachment of porous carbon microspheres, and will also affect the formation of mesopores and macropores to a certain extent.

[0091] As the amount of dopamine added increases, the amount of dopamine deposited on the surface of the organic template microspheres increases, which is conducive to the formation of a polydopamine layer with a stable structure and moderate thickness, and there is no excess dopamine that causes the carbon shell skeleton to be too thick or the pores to be blocked, so that the carbon shell skeleton structure can still be completely preserved after the organic template microspheres are removed later, without causing the collapse of the pore structure, which is conducive to increasing the number of micropores on the carbon shell skeleton. The prepared porous carbon material has an ideal hierarchical porous structure, including a large number of micropores, orderly arranged mesopores, and macropores formed by stacking gaps, which will greatly improve the electrochemical performance of the porous carbon material.

[0092] When the amount of dopamine added exceeds the upper limit of the range specified in the present invention, on the one hand, the polydopamine coating layer will be too thick, the thickness of the carbon shell skeleton formed after high-temperature carbonization will be too high, and the gas generated by the pyrolysis of the organic template microspheres will be difficult to break through the carbon shell skeleton and escape, resulting in a significant reduction in the number of micropores formed on the carbon shell skeleton; on the other hand, a portion of free irregular carbon material will be formed outside the carbon shell skeleton, so that the specific surface area and pore volume of the porous carbon material finally prepared are significantly reduced. This is because the amount of dopamine added in the system is too high, and the excess dopamine cannot be completely wrapped in On the surface of the organic template microspheres, the uncoated organic template microspheres undergo oxidative self-polymerization, and form free irregular carbon materials after carbonization. This part of irregular carbon material will adhere to the surface of the carbon shell skeleton in the form of physical deposition, and fill the gaps between the porous carbon microspheres, thereby reducing the number of macroporous structures of the porous carbon material; at the same time, it will also block some of the micropores and mesopores on the porous carbon material, thereby reducing the specific surface area and pore volume of the porous carbon material, causing the surface of the porous carbon material to change from a loose porous structure to a gully-like dense structure, which significantly affects the electrochemical properties of the porous carbon material.

[0093] In some optional examples, the organic template microspheres are added to the dopamine solution and mixed and stirred for 30 to 40 minutes, for example, 30 minutes, 31 minutes, 32 minutes, 33 minutes, 34 minutes, 35 minutes, 36 minutes, 37 minutes, 38 minutes, 39 minutes or 40 minutes; and then allowed to stand for 8 to 10 hours, for example, 8.0 hours, 8.2 hours, 8.4 hours, 8.6 hours, 8.8 hours, 9.0 hours, 9.2 hours, 9.4 hours, 9.6 hours, 9.8 hours or 10.0 hours, but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0094] In some optional instances, the mass ratio of the organic template microspheres in the template solution to the composite porous carbon precursor is 1:(1.3~1.5), for example, it can be 1:1.3, 1:1.32, 1:1.34, 1:1.36, 1:1.38, 1:1.4, 1:1.42, 1:1.44, 1:1.46, 1:1.48 or 1:1.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0095] In some optional examples, the composite porous carbon precursor is added to the template solution and mixed and stirred for 5 to 10 minutes, for example, 5.0 minutes, 5.5 minutes, 6.0 minutes, 6.5 minutes, 7.0 minutes, 7.5 minutes, 8.0 minutes, 8.5 minutes, 9.0 minutes, 9.5 minutes or 10.0 minutes; and then allowed to stand for 1 to 2 hours, for example, 1.0 hours, 1.1 hours, 1.2 hours, 1.3 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours or 2.0 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0096] As a preferred technical solution of the present invention, in step (III), the heating rate of the high-temperature carbonization is 3-5°C / min, for example, it can be 3.0°C / min, 3.2°C / min, 3.4°C / min, 3.6°C / min, 3.8°C / min, 4.0°C / min, 4.2°C / min, 4.4°C / min, 4.6°C / min, 4.8°C / min or 5.0°C / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0097] In some optional examples, the heating temperature of the high-temperature carbonization is 600~700℃, for example, it can be 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃ or 700℃, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0098] The present invention specifically limits the heating temperature of high-temperature carbonization to 600-700°C. When the carbonization temperature exceeds 700°C, the particles will seriously agglomerate, part of the pore structure will collapse, resulting in a decrease in porosity, which will inhibit the entry of electrolyte ions into the porous carbon material and charge storage.

[0099] In some optional examples, the holding time of the high temperature carbonization is 1 to 3 hours, for example, it can be 1.0h, 1.2h, 1.4h, 1.6h, 1.8h, 2.0h, 2.2h, 2.4h, 2.6h, 2.8h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0100] The present invention particularly limits the holding time of high-temperature carbonization to 1-3 hours. When the holding time is less than 1 hour, lignin and polydopamine are not fully carbonized, and the obtained products are mostly oligomer macromolecules, which is not conducive to the generation of carbon shell skeletons and porous carbon microspheres; when the holding time exceeds 3 hours, the generated porous carbon material is heavily cross-linked and agglomerated, resulting in an increase in size, a decrease in specific surface area, and a decrease in the contact area between the active substance and the electrolyte, which is not conducive to the electrolyte entering the pores more quickly and the transmission of ions, and the charge transfer resistance increases and the electrochemical performance decreases.

[0101] In some optional examples, the concentration of the hydrofluoric acid solution is 5 to 15 wt%, for example, it can be 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt% or 15 wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0102] In some optional examples, the immersion time of the composite carbide in the hydrofluoric acid solution is 10 to 20 hours, for example, it can be 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours or 20 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0103] As a preferred technical solution of the present invention, in step (IV), the mass ratio of the primary porous carbon material to the potassium carbonate is 1:(1~2), for example, it can be 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0104] The present invention particularly limits the mass ratio of primary porous carbon material to potassium carbonate to be 1: (1~2), and with the increase of potassium carbonate addition, the specific surface area and pore volume of the porous carbon material finally formed show a trend of increasing first and then decreasing, and activated etching pore-forming and mesoporous skeleton collapse will occur simultaneously during the pyrolysis activation process. When the addition of potassium carbonate is within the numerical range defined in the present invention, the activated etching pore-forming of potassium carbonate plays a major role, so both micropores and mesoporous pores are improved. When the addition of potassium carbonate reaches the upper limit of the range defined in the present invention, mesoporous skeleton collapse plays a leading role, and although micropores continue to be generated at this time, mesoporous pores will be reduced. When the addition of potassium carbonate continues to increase, potassium carbonate continues to etch the micropore wall, causing the micropores to become deeper and deeper and more and more difficult to be contacted and infiltrated by electrolyte ions. At the same time, when the amount of potassium carbonate added exceeds the upper limit of the range specified in the present invention, the pore size of the porous carbon material finally formed not only does not increase, but leads to a decrease in the pore volume. This is because when potassium carbonate is excessive, K2O and CO2 that do not react with the carbon surface inhibit the further decomposition of potassium carbonate, so that the potassium carbonate is not fully utilized.

[0105] In some optional examples, the pyrolysis activation process includes:

[0106] First, the activated mixture is heated to a first temperature at a first heating rate and kept warm, then, the activated mixture is continued to be heated to a second temperature at a second heating rate and kept warm, and finally, the activated mixture is heated to a third temperature at a third heating rate and kept warm, and after the insulation is completed, it is cooled to room temperature with the furnace to complete the pyrolysis activation and obtain the activated product.

[0107] In some optional instances, the first heating rate is 2~3℃ / min, for example, it can be 2.0℃ / min, 2.1℃ / min, 2.2℃ / min, 2.3℃ / min, 2.4℃ / min, 2.5℃ / min, 2.6℃ / min, 2.7℃ / min, 2.8℃ / min, 2.9℃ / min or 3.0℃ / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0108] In some optional instances, the first temperature is 200-300°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0109] In some optional examples, the activated mixture is kept at the first temperature for 30 to 40 minutes, for example, 30 minutes, 31 minutes, 32 minutes, 33 minutes, 34 minutes, 35 minutes, 36 minutes, 37 minutes, 38 minutes, 39 minutes or 40 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0110] In some optional instances, the second heating rate is 4-5°C / min, for example, it can be 4.0°C / min, 4.1°C / min, 4.2°C / min, 4.3°C / min, 4.4°C / min, 4.5°C / min, 4.6°C / min, 4.7°C / min, 4.8°C / min, 4.9°C / min or 5.0°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0111] In some optional instances, the second temperature is 500-600°C, for example, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C or 600°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0112] In some optional examples, the activated mixture is kept at the second temperature for 1 to 2 hours, for example, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0113] In some optional instances, the third heating rate is 6~8℃ / min, for example, it can be 6.0℃ / min, 6.2℃ / min, 6.4℃ / min, 6.6℃ / min, 6.8℃ / min, 7.0℃ / min, 7.2℃ / min, 7.4℃ / min, 7.6℃ / min, 7.8℃ / min or 8.0℃ / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0114] In some optional instances, the third temperature is 700-800°C, for example, it may be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C or 800°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0115] The present invention specifically limits the third temperature to 700-800°C. As the activation temperature increases, the pore volume of the prepared porous carbon material shows a trend of first increasing and then decreasing. This is because the increase in temperature is conducive to the reaction between the activator and the carbon, so the number of pores increases, and the pore volume and specific surface area increase. However, when the activation temperature exceeds 800°C, the pore volume of the porous carbon material finally formed decreases instead. This is because when the activation temperature reaches 800°C, it is close to the melting point of potassium carbonate (891°C). At the same time, in the presence of other substances, the melting point of potassium carbonate will be further reduced. Therefore, when the activation temperature exceeds 800°C, potassium carbonate will be molten, and the molten potassium carbonate will stop decomposing, thereby reducing the utilization rate of potassium carbonate.

[0116] In some optional examples, the activated mixture is kept at the third temperature for 2 to 3 hours, for example, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0117] In some optional examples, the washing process includes:

[0118] The activated product is washed with a hydrochloric acid solution, and then repeatedly rinsed with deionized water until it becomes neutral.

[0119] In some optional examples, the concentration of the hydrochloric acid solution is 0.5~1.5mol / L, for example, it can be 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L or 1.5mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0120] In a second aspect, the present invention provides an application of the method for preparing porous carbon material by microwave-assisted extraction of biomass lignin provided in the first aspect, wherein the porous carbon material prepared by the method is used for supercapacitors.

[0121] Compared with the prior art, the present invention has the following beneficial effects:

[0122] The present invention adopts microwave and ultrasound to jointly assist in extracting lignin from biomass, and uses nitrogen-phosphorus co-doped lignin as a microsphere carbon source, uses halloysite and nano-silica as microsphere hard templates, and forms nitrogen-phosphorus co-doped porous carbon microspheres after high-temperature carbonization and pyrolysis activation. Using polydopamine as a carbon shell skeleton carbon source, using organic template microspheres as a carbon shell hard template, a carbon shell skeleton is formed after high-temperature carbonization and pyrolysis activation, and finally a porous carbon material with a hierarchical porous structure is prepared. The porous carbon material prepared by the present invention is composed of a carbon shell skeleton and nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell skeleton, which has micropores, mesopores and macropores. The hierarchical porous structure can greatly shorten the diffusion path of electrolyte ions in the pores, effectively enhance the permeability of electrolytes to the internal surface of porous carbon materials, and provide short and low-resistance ion diffusion channels, which are conducive to the transmission of electrolyte ions in porous carbon materials, and meet the requirements of supercapacitors for excellent capacitance performance and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0123] Figure 1 A flow chart of the preparation process of preparing porous carbon materials by microwave-assisted extraction of biomass lignin provided in Examples 1-5 of the present invention;

[0124] Figure 2 is a scanning electron microscope image of the porous carbon precursor prepared in step (1) of Example 1 of the present invention;

[0125] Figure 3 is a transmission electron microscopy image of the porous carbon precursor prepared in step (1) of Example 1 of the present invention;

[0126] Figure 4 The infrared spectra of the composite porous carbon precursor prepared in step (2) of Example 1 of the present invention, the composite carbide obtained after high-temperature carbonization in step (3), and the primary porous carbon material obtained after immersion in a hydrofluoric acid solution to remove nano-silicon dioxide;

[0127] Figure 5 This is a scanning electron microscope image of nitrogen and phosphorus co-doped porous carbon microspheres prepared in Example 1 of the present invention;

[0128] Figure 6 This is a transmission electron micrograph of nitrogen and phosphorus co-doped porous carbon microspheres prepared in Example 1 of the present invention;

[0129] Figure 7 This is a mapping diagram of nitrogen and phosphorus elements in the nitrogen-phosphorus co-doped porous carbon microspheres prepared in Example 1 of the present invention;

[0130] Figure 8 This is a scanning electron microscope image of the porous carbon material prepared in Example 1 of the present invention;

[0131] Fig. 9 This is a transmission electron microscope image of the porous carbon material prepared in Example 1 of the present invention;

[0132] Fig.10 Cyclic voltammetry curves of the porous carbon materials prepared in Example 1 and Comparative Examples 1-4 of the present invention obtained in electrochemical tests;

[0133] Fig.11 The constant current charge-discharge curves of the porous carbon materials prepared in Example 1 and Comparative Examples 1-4 of the present invention obtained in electrochemical tests. DETAILED DESCRIPTION

[0134] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0135] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications, manufacturers and other information are as follows:

[0136] Ethylene glycol: B25695-5ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0137] 1,4-Butanediol: S24138-500ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0138] Acetone: purity>99%, purchased from Nanjing Chemical Reagent Co., Ltd.;

[0139] Methanol: purity >99%, purchased from Nanjing Chemical Reagent Co., Ltd.;

[0140] Anhydrous ethanol: purity>90%, purchased from Nanjing Chemical Reagent Co., Ltd.;

[0141] Chitosan: purity >90%, purchased from Shandong Haiyihua Biotechnology Co., Ltd.;

[0142] Sodium dihydrogen phosphate: S24161-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0143] Halloysite: purity >95%, purchased from Xi'an Ruixi Biotechnology Co., Ltd.;

[0144] Hexadecyltrimethylammonium bromide: S15001-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0145] Ammonia: F20190001887, purchased from Nanjing Chemical Reagent Co., Ltd.

[0146] Tetraethyl orthosilicate: purity>99%, purchased from Wuhan Jiyesheng Chemical Co., Ltd.;

[0147] Dopamine: purity>99%, purchased from Chengdu Huaxia Chemical Reagent Co., Ltd.;

[0148] Tris-HCl buffer: GL1642, purchased from Beijing Biolab Technology Co., Ltd.;

[0149] Polystyrene organic template microspheres: average particle size 4-5 μm, purchased from Xi'an Ruixi Biotechnology Co., Ltd.;

[0150] Hydrofluoric acid: purity>99%, purchased from Zibo Lishuo Chemical Trading Co., Ltd.;

[0151] Potassium carbonate: purity>99%, purchased from Shandong Zhengxing New Materials Co., Ltd.

[0152] Example 1

[0153] This embodiment provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. Figure 1 As shown, the method specifically comprises the following steps:

[0154] (1) The corn stalks were crushed, passed through a 100-mesh sieve, and frozen with liquid nitrogen to obtain biomass powder. The liquid nitrogen freezing process was as follows: the biomass powder was immersed in liquid nitrogen for 3 minutes, then taken out and immersed in liquid nitrogen again, and this process was repeated 8 times.

[0155] The biomass powder is dispersed in an ethanol aqueous solution to form a biomass dispersion, wherein the volume fraction of ethanol in the ethanol aqueous solution is 30%, and the mass ratio of the biomass powder to the ethanol aqueous solution is 0.1:1; the biomass dispersion is preheated by microwave for 5 minutes, the microwave power is 800W, and the microwave frequency is 600MHz; then the biomass dispersion is simultaneously subjected to ultrasonic treatment and microwave treatment for 10 minutes, the ultrasonic power is 2000W, the ultrasonic frequency is 1.5MHz, the microwave power is 3000W, and the microwave frequency is 1500MHz;

[0156] After the treatment, the treated product was extracted with ethylene glycol for 50 minutes, the extraction temperature was 60°C, and the solid-liquid ratio was 1g:20mL; after the extraction, the extraction solution was filtered to obtain a filtrate, and a 1.5 mol / L hydrochloric acid solution was added to the filtrate to adjust the pH value of the filtrate to 5, followed by centrifugation, and the precipitate was dried to obtain lignin;

[0157] Dispersing lignin in deionized water to obtain a lignin solution, wherein the mass ratio of lignin to deionized water is 1:20, dropping 8 wt % acetic acid solution into the lignin solution to adjust the pH value of the lignin solution to 6, then sequentially adding chitosan and sodium dihydrogen phosphate into the lignin solution, wherein the mass ratio of lignin, chitosan and sodium dihydrogen phosphate is 1:0.4:0.6, and mixing and stirring to obtain a precursor solution;

[0158] Adding halloysite to the precursor solution, the mass ratio of halloysite to lignin in the precursor solution is 1:1.2, and ultrasonically dispersing the solution for 40 minutes at an ultrasonic power of 200 W to obtain a suspension; placing the suspension under a negative pressure environment of -0.5 MPa for 2.5 hours, and then centrifuging it at a speed of 2000 r / min for 2 hours, washing the precipitate after centrifugation, and freeze-drying it at -40°C for 36 hours after washing to neutrality to obtain a porous carbon precursor;

[0159] (2) dissolving hexadecyltrimethylammonium bromide in anhydrous ethanol to obtain a dispersed solution, wherein the mass fraction of hexadecyltrimethylammonium bromide in the dispersed solution is 3 wt %, adding 22 wt % ammonia solution and the porous carbon precursor obtained in step (1) to the dispersed solution, wherein the ratio of hexadecyltrimethylammonium bromide, ammonia solution and porous carbon precursor is 5 g:30 mL:1 g, mixing and stirring, and ultrasonically dispersing at an ultrasonic power of 400 W for 30 min to obtain a reaction precursor solution;

[0160] TEOS, ethanol and deionized water were mixed and stirred in a volume ratio of 1:1.6:0.2 to obtain a TEOS solution, 1 mol / L nitric acid solution was added dropwise to the TEOS solution to adjust the pH value of the TEOS solution to 5, and then the TEOS solution was stirred for 5 hours to obtain a hydrolyzate;

[0161] Adding a reaction precursor solution to the hydrolyzate while stirring, the hydrolyzate and the reaction precursor solution are mixed according to a volume ratio of 1:3 of tetraethyl orthosilicate to an ammonia solution to obtain a composite precursor sol; allowing the composite precursor sol to stand for aging at a constant temperature of 40° C. for 5 hours to obtain a composite precursor gel; freeze-drying the composite precursor gel at -40° C. for 36 hours to obtain a composite porous carbon precursor, which consists of a porous carbon precursor and nano-silicon dioxide coated on the surface thereof;

[0162] (3) dissolving dopamine in Tris-HCl buffer to obtain a dopamine solution with a pH value of 8, wherein the concentration of dopamine in the dopamine solution is 5 g / L; adding polystyrene organic template microspheres with an average particle size of 4 μm to the dopamine solution, wherein the mass ratio of the polystyrene organic template microspheres to dopamine is 1:4, mixing and stirring for 30 minutes and then standing for 10 hours to form a polydopamine coating layer on the surface of the polystyrene organic template microspheres, thereby obtaining a template solution;

[0163] Subsequently, the composite porous carbon precursor obtained in step (2) is added to the template solution, the mass ratio of the polystyrene organic template microspheres to the composite porous carbon precursor is 1:1.3, the mixture is stirred for 5 minutes and then allowed to stand for 2 hours, so that the composite porous carbon precursor is loaded on the surface of the polydopamine coating layer to obtain a reaction solution, and the reaction solution is filtered, washed and dried to obtain composite precursor particles;

[0164] The composite precursor particles are heated to 600°C at a heating rate of 3°C / min and kept warm for 3 hours. After the heat preservation, they are cooled to room temperature with the furnace to complete high-temperature carbonization and obtain composite carbides. Subsequently, the composite carbides are immersed in a 5wt% hydrofluoric acid solution, and after immersion for 20 hours, they are filtered, washed and dried to obtain a primary porous carbon material, which consists of a carbon shell and nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell.

[0165] (4) uniformly mixing the primary porous carbon material obtained in step (3) with potassium carbonate in a mass ratio of 1:1 and fully grinding to obtain an activated mixture; spreading the activated mixture evenly in a porcelain boat, placing the porcelain boat in a horizontal tube furnace, and pyrolyzing and activating the activated mixture under a nitrogen atmosphere. The pyrolysis and activation process includes:

[0166] First, the activated mixture was heated to 200°C at a heating rate of 2°C / min and kept warm for 40 minutes; then, the activated mixture was heated to 500°C at a heating rate of 4°C / min and kept warm for 2 hours; finally, the activated mixture was heated to 700°C at a heating rate of 6°C / min and kept warm for 3 hours. After the insulation was completed, it was cooled to room temperature with the furnace to complete the pyrolysis activation and obtain the activated product;

[0167] After the pyrolysis activation is completed, the activated product is washed with a 0.5 mol / L hydrochloric acid solution, and then the activated product is repeatedly rinsed with deionized water until it is neutral, thereby obtaining the porous carbon material.

[0168] Figure 2 and Figure 3 The scanning electron microscope image and transmission electron microscope image of the porous carbon precursor prepared in step (1) of this embodiment are shown in the figure. It can be seen from the figure that the porous carbon precursor is a spherical structure with developed pores, which is formed by the aggregation of halloysite under the action of dehydration and hydrogen bonding.

[0169] Figure 4 The infrared spectra of the composite porous carbon precursor prepared in step (2) of this embodiment, the composite carbide obtained after high-temperature carbonization in step (3), and the primary porous carbon material obtained after soaking in hydrofluoric acid to remove halloysite and nano-silicon dioxide. It can be seen from the figure that in the infrared spectrum of the composite porous carbon precursor, the -1 The characteristic peak is attributed to the stretching vibration peak of -OH, which comes from the inherent -OH on the surface of the composite porous carbon precursor or H2O absorbed by the composite. -1 and 1625cm -1 The characteristic peaks are attributed to the antisymmetric stretching vibration peak of the CO bond and the symmetric stretching vibration peak of the C=C bond, which are located at 805cm -1 and 470cm -1 The characteristic peaks belong to the bending vibration peak and symmetric stretching vibration peak of Si-O-Si, indicating that ethyl orthosilicate was hydrolyzed in the system and nano-silicon dioxide was generated.

[0170] Comparing the infrared spectra of the composite porous carbon precursor with that of the composite carbide, it can be seen that after the carbonization treatment of the composite porous carbon precursor, the characteristic peaks of methyl and methylene (2920 cm -1 and 2855cm -1 ) almost completely disappeared, while the characteristic peaks attributed to silica and carbon skeleton structure did not change significantly, which indicates that during the high-temperature carbonization process, the polystyrene organic template microspheres were completely pyrolyzed by high temperature and no additional treatment was needed to remove the organic template microspheres.

[0171] Comparing the infrared spectra of the composite carbide with that of the primary porous carbon material, it can be seen that by immersing in a hydrofluoric acid solution to remove nano-silica in the composite carbide, the characteristic peaks of silica almost disappear, while the carbon-based characteristic peaks in the composite carbide are well retained, which indicates that the silica in the composite carbide can be successfully removed while effectively retaining the porous carbon skeleton by treatment with a hydrofluoric acid solution.

[0172] Figure 5 and Figure 6The scanning electron microscope images and transmission electron microscope images of the nitrogen-phosphorus co-doped porous carbon microspheres prepared in this embodiment are respectively. It can be seen from the figures that a rich ordered mesoporous structure is formed inside the nitrogen-phosphorus co-doped porous carbon microspheres, and the mesoporous structure can be used as an ion transmission channel, thereby improving the transmission efficiency of electrolyte ions in the porous carbon microspheres; at the same time, pits left by the high-temperature carbonization of nano-silicon dioxide are also formed on the surface of the nitrogen-phosphorus co-doped porous carbon microspheres, which can not only serve as ion buffer-storage containers, but also realize the opening of the ordered mesoporous channels inside the porous carbon microspheres, so that the ordered mesoporous channels inside the porous carbon microspheres are connected to the surfaces of the porous carbon microspheres, and the electrolyte ions can enter the ordered mesoporous channels inside the porous carbon microspheres from the surfaces of the porous carbon microspheres more quickly.

[0173] Figure 7 This is a mapping diagram of nitrogen and phosphorus elements in the nitrogen-phosphorus co-doped porous carbon microspheres prepared in this embodiment. It can be seen from the figure that there are a large amount of nitrogen and phosphorus elements in the porous carbon microspheres, which indicates that the present invention achieves nitrogen-phosphorus co-doping of porous carbon microspheres through chitosan and sodium dihydrogen phosphate.

[0174] Figure 8 and Fig. 9 The scanning electron microscope images and transmission electron microscope images of the porous carbon material prepared in this embodiment are respectively. It can be seen from the figures that the porous carbon material is composed of a carbon shell skeleton and nitrogen and phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell skeleton, forming a hierarchical porous structure with rich micropores, ordered mesopores and interstitial macropores. This special structure can greatly shorten the diffusion path of electrolyte ions in the pores, effectively enhance the permeability of electrolyte to the internal surface of the porous carbon material, and provide a short and low-resistance ion diffusion channel, which is beneficial to the transmission of electrolyte ions in the porous carbon material, and meets the requirements of supercapacitors for excellent capacitance performance and high rate performance.

[0175] Example 2

[0176] This embodiment provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. Figure 1 As shown, the method specifically comprises the following steps:

[0177] (1) The rice straw was crushed, passed through a 120-mesh sieve, and frozen in liquid nitrogen to obtain biomass powder. The liquid nitrogen freezing process was as follows: the biomass powder was immersed in liquid nitrogen for 3.5 min, then taken out and immersed in liquid nitrogen again, and this process was repeated 7 times.

[0178] The biomass powder is dispersed in an ethanol aqueous solution to form a biomass dispersion, wherein the volume fraction of ethanol in the ethanol aqueous solution is 32%, and the mass ratio of the biomass powder to the ethanol aqueous solution is 0.15:1; the biomass dispersion is preheated by microwave for 6 minutes, the microwave power is 780W, and the microwave frequency is 580MHz; then the biomass dispersion is simultaneously subjected to ultrasonic treatment and microwave treatment for 12 minutes, the ultrasonic power is 1800W, the ultrasonic frequency is 1.2MHz, the microwave power is 2800W, and the microwave frequency is 1300MHz;

[0179] After the treatment, the treated product was extracted with 1,4-butanediol for 52 minutes, the extraction temperature was 65°C, and the solid-liquid ratio was 1g:18mL; after the extraction, the extraction solution was filtered to obtain a filtrate, and a 1.8 mol / L hydrochloric acid solution was added to the filtrate to adjust the pH value of the filtrate to 4.5, followed by centrifugation, and the precipitate was dried to obtain lignin;

[0180] Dispersing lignin in deionized water to obtain a lignin solution, wherein the mass ratio of lignin to deionized water is 1:22, adding 9wt% acetic acid solution dropwise to the lignin solution to adjust the pH value of the lignin solution to 5.8, then sequentially adding chitosan and sodium dihydrogen phosphate to the lignin solution, wherein the mass ratio of lignin, chitosan and sodium dihydrogen phosphate is 1:0.42:0.62, and mixing and stirring to obtain a precursor solution;

[0181] Adding halloysite to the precursor solution, the mass ratio of halloysite to lignin in the precursor solution is 1:1.25, and ultrasonically dispersing for 38 minutes at an ultrasonic power of 220 W to obtain a suspension; placing the suspension in a negative pressure environment of -0.55 MPa for 2.2 hours, and then centrifuging at a speed of 2200 r / min for 1.8 hours, washing the precipitate after centrifugation, washing to neutrality, and freeze-drying at -42°C for 32 hours to obtain a porous carbon precursor;

[0182] (2) dissolving hexadecyltrimethylammonium bromide in anhydrous ethanol to obtain a dispersed solution, wherein the mass fraction of hexadecyltrimethylammonium bromide in the dispersed solution is 3.5 wt %, adding 23 wt % ammonia solution and the porous carbon precursor obtained in step (1) to the dispersed solution, wherein the ratio of hexadecyltrimethylammonium bromide, ammonia solution and porous carbon precursor is 5.2 g:35 mL:1 g, mixing and stirring, and ultrasonically dispersing at an ultrasonic power of 420 W for 28 min to obtain a reaction precursor solution;

[0183] TEOS, ethanol and deionized water were mixed and stirred in a volume ratio of 1:1.62:0.22 to obtain a TEOS solution, 1.2 mol / L nitric acid solution was added dropwise to the TEOS solution to adjust the pH value of the TEOS solution to 4.8, and then the TEOS solution was stirred for 5.2 h to obtain a hydrolyzate;

[0184] Adding the reaction precursor solution to the hydrolyzate while stirring, the hydrolyzate and the reaction precursor solution are mixed according to a volume ratio of 1:3.5 of tetraethyl orthosilicate to an ammonia solution to obtain a composite precursor sol; allowing the composite precursor sol to stand for aging at a constant temperature of 41° C. for 4.5 hours to obtain a composite precursor gel; freeze-drying the composite precursor gel at -42° C. for 32 hours to obtain a composite porous carbon precursor, wherein the composite porous carbon precursor consists of a porous carbon precursor and nano-silicon dioxide coated on the surface thereof;

[0185] (3) dissolving dopamine in Tris-HCl buffer to obtain a dopamine solution with a pH value of 8.2, wherein the concentration of dopamine in the dopamine solution is 6 g / L; adding polystyrene organic template microspheres with an average particle size of 4.2 μm to the dopamine solution, wherein the mass ratio of the polystyrene organic template microspheres to dopamine is 1:4.2, mixing and stirring for 32 minutes, and then standing for 9.5 hours to form a polydopamine coating layer on the surface of the polystyrene organic template microspheres, thereby obtaining a template solution;

[0186] Subsequently, the composite porous carbon precursor obtained in step (2) is added to the template solution, the mass ratio of the polystyrene organic template microspheres to the composite porous carbon precursor is 1:1.35, the mixture is mixed and stirred for 6 minutes and then allowed to stand for 1.8 hours, so that the composite porous carbon precursor is loaded on the surface of the polydopamine coating layer to obtain a reaction solution, and the reaction solution is filtered, washed and dried to obtain composite precursor particles;

[0187] The composite precursor particles were heated to 620°C at a heating rate of 3.5°C / min and kept warm for 2.5 hours. After the heat preservation, they were cooled to room temperature with the furnace to complete high-temperature carbonization and obtain composite carbides. Subsequently, the composite carbides were immersed in an 8wt% hydrofluoric acid solution, and after immersion for 18 hours, they were filtered, washed and dried to obtain a primary porous carbon material, which consisted of a carbon shell and nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell.

[0188] (4) uniformly mixing the primary porous carbon material obtained in step (3) with potassium carbonate in a mass ratio of 1:1.2 and fully grinding to obtain an activated mixture; spreading the activated mixture in a porcelain boat, placing the porcelain boat in a horizontal tube furnace, and pyrolyzing and activating the activated mixture under a nitrogen atmosphere. The pyrolysis and activation process includes:

[0189] First, the activated mixture was heated to 220°C at a heating rate of 2.2°C / min and kept warm for 38 minutes; then, the activated mixture was heated to 520°C at a heating rate of 4.2°C / min and kept warm for 1.8 hours; finally, the activated mixture was heated to 720°C at a heating rate of 6.5°C / min and kept warm for 2.8 hours. After the insulation was completed, it was cooled to room temperature in the furnace to complete the pyrolysis activation and obtain the activated product;

[0190] After the pyrolysis activation is completed, the activated product is washed with a 0.8 mol / L hydrochloric acid solution, and then the activated product is repeatedly rinsed with deionized water until it is neutral, thereby obtaining the porous carbon material.

[0191] Example 3

[0192] This embodiment provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. Figure 1 As shown, the method specifically comprises the following steps:

[0193] (1) Wheat straw was crushed, passed through a 150-mesh sieve, and frozen in liquid nitrogen to obtain biomass powder. The liquid nitrogen freezing process was as follows: the biomass powder was immersed in liquid nitrogen for 4 minutes, then taken out and immersed in liquid nitrogen again, and this process was repeated 7 times;

[0194] The biomass powder is dispersed in an ethanol aqueous solution to form a biomass dispersion, wherein the volume fraction of ethanol in the ethanol aqueous solution is 35%, and the mass ratio of the biomass powder to the ethanol aqueous solution is 0.2:1; the biomass dispersion is preheated by microwave for 7 minutes, the microwave power is 750W, and the microwave frequency is 550MHz; then the biomass dispersion is simultaneously subjected to ultrasonic treatment and microwave treatment for 15 minutes, the ultrasonic power is 1500W, the ultrasonic frequency is 1MHz, the microwave power is 2500W, and the microwave frequency is 1200MHz;

[0195] After the treatment, the treated product was extracted with acetone for 55 minutes, the extraction temperature was 70°C, and the solid-liquid ratio was 1g:15mL; after the extraction, the extraction solution was filtered to obtain a filtrate, and a 2mol / L hydrochloric acid solution was added to the filtrate to adjust the pH value of the filtrate to 4, followed by centrifugation, and the precipitate was dried to obtain lignin;

[0196] Dispersing lignin in deionized water to obtain a lignin solution, wherein the mass ratio of lignin to deionized water is 1:25, and dropping 10 wt % acetic acid solution into the lignin solution to adjust the pH value of the lignin solution to 5.5, and then sequentially adding chitosan and sodium dihydrogen phosphate into the lignin solution, wherein the mass ratio of lignin, chitosan and sodium dihydrogen phosphate is 1:0.45:0.65, and mixing and stirring to obtain a precursor solution;

[0197] Adding halloysite to the precursor solution, the mass ratio of halloysite to lignin in the precursor solution is 1:1.3, and ultrasonically dispersing for 35 minutes at an ultrasonic power of 250 W to obtain a suspension; placing the suspension at a negative pressure of -0.6 MPa for 2 hours, and then centrifuging at a speed of 2500 r / min for 1.5 hours, washing the precipitate after centrifugation, washing to neutrality, and freeze-drying at -45°C for 30 hours to obtain a porous carbon precursor;

[0198] (2) dissolving hexadecyltrimethylammonium bromide in anhydrous ethanol to obtain a dispersed solution, wherein the mass fraction of hexadecyltrimethylammonium bromide in the dispersed solution is 4 wt %, adding a 24 wt % ammonia solution and the porous carbon precursor obtained in step (1) to the dispersed solution, wherein the ratio of hexadecyltrimethylammonium bromide, ammonia solution and porous carbon precursor is 5.5 g:40 mL:1 g, mixing and stirring, and ultrasonically dispersing at an ultrasonic power of 450 W for 25 min to obtain a reaction precursor solution;

[0199] TEOS, ethanol and deionized water were mixed and stirred in a volume ratio of 1:1.65:0.25 to obtain a TEOS solution, 1.5 mol / L nitric acid solution was added dropwise to the TEOS solution to adjust the pH value of the TEOS solution to 4.5, and then the TEOS solution was stirred for 5.5 h to obtain a hydrolyzate;

[0200] The reaction precursor solution is added to the hydrolyzate while stirring, and the hydrolyzate and the reaction precursor solution are mixed according to a volume ratio of 1:4 of tetraethyl orthosilicate to an ammonia solution to obtain a composite precursor sol; the composite precursor sol is allowed to stand and age for 4 hours at a constant temperature of 42° C. to obtain a composite precursor gel; the composite precursor gel is freeze-dried at -45° C. for 30 hours to obtain a composite porous carbon precursor, which consists of a porous carbon precursor and nano-silicon dioxide coated on the surface thereof;

[0201] (3) dissolving dopamine in Tris-HCl buffer to obtain a dopamine solution with a pH value of 8.5, wherein the concentration of dopamine in the dopamine solution is 7 g / L; adding polystyrene organic template microspheres with an average particle size of 4.5 μm to the dopamine solution, wherein the mass ratio of the polystyrene organic template microspheres to dopamine is 1:4.5, mixing and stirring for 35 minutes and then standing for 9 hours to form a polydopamine coating layer on the surface of the polystyrene organic template microspheres, thereby obtaining a template solution;

[0202] Subsequently, the composite porous carbon precursor obtained in step (2) is added to the template solution, the mass ratio of the polystyrene organic template microspheres to the composite porous carbon precursor is 1:1.4, the mixture is stirred for 7 minutes and then allowed to stand for 1.5 hours, so that the composite porous carbon precursor is loaded on the surface of the polydopamine coating layer to obtain a reaction solution, and the reaction solution is filtered, washed and dried to obtain composite precursor particles;

[0203] The composite precursor particles were heated to 650°C at a heating rate of 4°C / min and kept warm for 2 hours. After the heat preservation, they were cooled to room temperature with the furnace to complete high-temperature carbonization and obtain composite carbides. Subsequently, the composite carbides were immersed in a 10wt% hydrofluoric acid solution, and after immersion for 15 hours, they were filtered, washed and dried to obtain a primary porous carbon material, which consisted of a carbon shell and nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell.

[0204] (4) uniformly mixing the primary porous carbon material obtained in step (3) with potassium carbonate in a mass ratio of 1:1.5 and fully grinding to obtain an activated mixture; spreading the activated mixture in a porcelain boat, placing the porcelain boat in a horizontal tube furnace, and pyrolyzing and activating the activated mixture under a nitrogen atmosphere. The pyrolysis and activation process includes:

[0205] First, the activated mixture was heated to 250°C at a heating rate of 2.5°C / min and kept warm for 35 minutes; then, the activated mixture was heated to 550°C at a heating rate of 4.5°C / min and kept warm for 1.5 hours; finally, the activated mixture was heated to 750°C at a heating rate of 7°C / min and kept warm for 2.5 hours. After the insulation was completed, it was cooled to room temperature in the furnace to complete the pyrolysis activation and obtain the activated product;

[0206] After the pyrolysis activation is completed, the activated product is washed with a 1 mol / L hydrochloric acid solution, and then the activated product is repeatedly rinsed with deionized water until it is neutral, thereby obtaining the porous carbon material.

[0207] Example 4

[0208] This embodiment provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. Figure 1 As shown, the method specifically comprises the following steps:

[0209] (1) The wood chips were crushed, passed through a 180-mesh sieve, and frozen with liquid nitrogen to obtain biomass powder. The liquid nitrogen freezing process was as follows: the biomass powder was immersed in liquid nitrogen for 4.5 minutes, then taken out and immersed in liquid nitrogen again, and this process was repeated 6 times;

[0210] The biomass powder is dispersed in an ethanol aqueous solution to form a biomass dispersion, wherein the volume fraction of ethanol in the ethanol aqueous solution is 38%, and the mass ratio of the biomass powder to the ethanol aqueous solution is 0.25:1; the biomass dispersion is preheated by microwave for 7 minutes, the microwave power is 720W, and the microwave frequency is 520MHz; then the biomass dispersion is simultaneously subjected to ultrasonic treatment and microwave treatment for 18 minutes, the ultrasonic power is 1200W, the ultrasonic frequency is 0.8MHz, the microwave power is 2200W, and the microwave frequency is 1100MHz;

[0211] After the treatment, the treated product was extracted with acetone for 58 minutes at a temperature of 75°C and a solid-liquid ratio of 1 g:12 mL. After the extraction, the extracted solution was filtered to obtain a filtrate, and a 2.2 mol / L hydrochloric acid solution was added to the filtrate to adjust the pH value of the filtrate to 3.5, followed by centrifugation, and the precipitate was dried to obtain lignin.

[0212] Dispersing lignin in deionized water to obtain a lignin solution, wherein the mass ratio of lignin to deionized water is 1:28, and dropping 11 wt % acetic acid solution into the lignin solution to adjust the pH value of the lignin solution to 5.2, and then sequentially adding chitosan and sodium dihydrogen phosphate into the lignin solution, wherein the mass ratio of lignin, chitosan and sodium dihydrogen phosphate is 1:0.48:0.68, and mixing and stirring to obtain a precursor solution;

[0213] Adding halloysite to the precursor solution, the mass ratio of halloysite to lignin in the precursor solution is 1:1.35, and ultrasonically dispersing for 32 minutes at an ultrasonic power of 280 W to obtain a suspension; placing the suspension in a negative pressure environment of -0.65 MPa for 1.8 hours, and then centrifuging at a speed of 2800 r / min for 1.2 hours, washing the precipitate after centrifugation, washing to neutrality, and freeze-drying it at -48°C for 28 hours to obtain a porous carbon precursor;

[0214] (2) dissolving hexadecyltrimethylammonium bromide in anhydrous ethanol to obtain a dispersed solution, wherein the mass fraction of hexadecyltrimethylammonium bromide in the dispersed solution is 4.5 wt %, adding a 24 wt % ammonia solution and the porous carbon precursor obtained in step (1) to the dispersed solution, wherein the ratio of hexadecyltrimethylammonium bromide, ammonia solution and porous carbon precursor is 5.8 g:45 mL:1 g, mixing and stirring, and ultrasonically dispersing at an ultrasonic power of 480 W for 22 min to obtain a reaction precursor solution;

[0215] TEOS, ethanol and deionized water were mixed and stirred in a volume ratio of 1:1.68:0.28 to obtain a TEOS solution, 1.8 mol / L nitric acid solution was added dropwise to the TEOS solution to adjust the pH value of the TEOS solution to 4.2, and then the TEOS solution was stirred for 5.8 h to obtain a hydrolyzate;

[0216] The reaction precursor solution is added to the hydrolyzate while stirring, and the hydrolyzate and the reaction precursor solution are mixed according to a volume ratio of 1:4.5 of tetraethyl orthosilicate to an ammonia solution to obtain a composite precursor sol; the composite precursor sol is allowed to stand and age for 3.5 hours at a constant temperature of 43° C. to obtain a composite precursor gel; the composite precursor gel is freeze-dried at -48° C. for 28 hours to obtain a composite porous carbon precursor, which consists of a porous carbon precursor and nano-silicon dioxide coated on the surface thereof;

[0217] (3) dissolving dopamine in Tris-HCl buffer to obtain a dopamine solution with a pH value of 8.8, wherein the concentration of dopamine in the dopamine solution is 7 g / L; adding polystyrene organic template microspheres with an average particle size of 4.8 μm to the dopamine solution, wherein the mass ratio of the polystyrene organic template microspheres to dopamine is 1:4.8, mixing and stirring for 38 minutes, and then standing for 8.5 hours to form a polydopamine coating layer on the surface of the polystyrene organic template microspheres, thereby obtaining a template solution;

[0218] Subsequently, the composite porous carbon precursor obtained in step (2) is added to the template solution, the mass ratio of the polystyrene organic template microspheres to the composite porous carbon precursor is 1:1.45, the mixture is mixed and stirred for 8 minutes and then allowed to stand for 1.2 hours, so that the composite porous carbon precursor is loaded on the surface of the polydopamine coating layer to obtain a reaction solution, and the reaction solution is filtered, washed and dried to obtain composite precursor particles;

[0219] The composite precursor particles were heated to 680°C at a heating rate of 4.5°C / min and kept warm for 1.5 hours. After the heat preservation, they were cooled to room temperature with the furnace to complete high-temperature carbonization and obtain composite carbides. Subsequently, the composite carbides were immersed in a 12wt% hydrofluoric acid solution, and after immersion for 12 hours, they were filtered, washed and dried to obtain a primary porous carbon material, which consisted of a carbon shell and nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell.

[0220] (4) uniformly mixing the primary porous carbon material obtained in step (3) with potassium carbonate in a mass ratio of 1:1.8 and fully grinding to obtain an activated mixture; spreading the activated mixture in a porcelain boat, placing the porcelain boat in a horizontal tube furnace, and pyrolyzing and activating the activated mixture under a nitrogen atmosphere. The pyrolysis and activation process includes:

[0221] First, the activated mixture was heated to 280°C at a heating rate of 2.8°C / min and kept warm for 32 minutes; then, the activated mixture was heated to 580°C at a heating rate of 4.8°C / min and kept warm for 1.2 hours; finally, the activated mixture was heated to 780°C at a heating rate of 7.5°C / min and kept warm for 2.2 hours. After the insulation was completed, it was cooled to room temperature in the furnace to complete the pyrolysis activation and obtain the activated product;

[0222] After the pyrolysis activation is completed, the activated product is washed with a 1.2 mol / L hydrochloric acid solution, and then repeatedly rinsed with deionized water until it is neutral to obtain the porous carbon material.

[0223] Example 5

[0224] This embodiment provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. Figure 1 As shown, the method specifically comprises the following steps:

[0225] (1) Sawdust is crushed, passed through a 200-mesh sieve, and frozen with liquid nitrogen to obtain biomass powder. The operation process of liquid nitrogen freezing is as follows: the biomass powder is immersed in liquid nitrogen, and the immersion stays for 5 minutes, then taken out, and immersed in liquid nitrogen again, and this is repeated 5 times;

[0226] The biomass powder is dispersed in an ethanol-water solution to form a biomass dispersion, wherein the volume fraction of ethanol in the ethanol-water solution is 40%, and the mass ratio of the biomass powder to the ethanol-water solution is 0.3:1; the biomass dispersion is preheated by microwave for 8 minutes, the microwave power is 700 W, and the microwave frequency is 500 MHz; then the biomass dispersion is simultaneously subjected to ultrasonic treatment and microwave treatment for 20 minutes, the ultrasonic power is 1000 W, the ultrasonic frequency is 0.5 MHz, the microwave power is 2000 W, and the microwave frequency is 1000 MHz;

[0227] After the treatment, the treated product was extracted with methanol for 60 minutes, the extraction temperature was 80°C, and the solid-liquid ratio was 1g:10mL; after the extraction, the extraction solution was filtered to obtain a filtrate, and a 2.5 mol / L hydrochloric acid solution was added to the filtrate to adjust the pH value of the filtrate to 3, followed by centrifugation, and the precipitate was dried to obtain lignin;

[0228] Dispersing lignin in deionized water to obtain a lignin solution, wherein the mass ratio of lignin to deionized water is 1:30, and dropping 12 wt % acetic acid solution into the lignin solution to adjust the pH value of the lignin solution to 5, and then sequentially adding chitosan and sodium dihydrogen phosphate into the lignin solution, wherein the mass ratio of lignin, chitosan and sodium dihydrogen phosphate is 1:0.5:0.7, and mixing and stirring to obtain a precursor solution;

[0229] Adding halloysite to the precursor solution, the mass ratio of halloysite to lignin in the precursor solution is 1:1.4, and ultrasonically dispersing for 30 minutes at an ultrasonic power of 300 W to obtain a suspension; placing the suspension in a negative pressure environment of -0.7 MPa for 1.5 hours, and then centrifuging at a speed of 3000 r / min for 1 hour, washing the precipitate after centrifugation, washing to neutrality, and freeze-drying at -50°C for 24 hours to obtain a porous carbon precursor;

[0230] (2) dissolving hexadecyltrimethylammonium bromide in anhydrous ethanol to obtain a dispersed solution, wherein the mass fraction of hexadecyltrimethylammonium bromide in the dispersed solution is 5 wt %, adding 25 wt % ammonia solution and the porous carbon precursor obtained in step (1) to the dispersed solution, wherein the ratio of hexadecyltrimethylammonium bromide, ammonia solution and porous carbon precursor is 6 g:50 mL:1 g, mixing and stirring, and ultrasonically dispersing at an ultrasonic power of 500 W for 20 min to obtain a reaction precursor solution;

[0231] TEOS, ethanol and deionized water were mixed and stirred in a volume ratio of 1:1.7:0.3 to obtain a TEOS solution, 2 mol / L nitric acid solution was added dropwise to the TEOS solution to adjust the pH value of the TEOS solution to 4, and then the TEOS solution was stirred for 6 hours to obtain a hydrolyzate;

[0232] Adding the reaction precursor solution to the hydrolyzate while stirring, the hydrolyzate and the reaction precursor solution are mixed according to a volume ratio of 1:5 of tetraethyl orthosilicate to an ammonia solution to obtain a composite precursor sol; allowing the composite precursor sol to stand for aging at a constant temperature of 45° C. for 3 hours to obtain a composite precursor gel; freeze-drying the composite precursor gel at -50° C. for 24 hours to obtain a composite porous carbon precursor, which consists of a porous carbon precursor and nano-silicon dioxide coated on the surface thereof;

[0233] (3) dissolving dopamine in Tris-HCl buffer to obtain a dopamine solution with a pH value of 9, wherein the concentration of dopamine in the dopamine solution is 8 g / L; adding polystyrene organic template microspheres with an average particle size of 5 μm to the dopamine solution, wherein the mass ratio of the polystyrene organic template microspheres to dopamine is 1:5, mixing and stirring for 40 minutes and then standing for 8 hours to form a polydopamine coating layer on the surface of the polystyrene organic template microspheres, thereby obtaining a template solution;

[0234] Subsequently, the composite porous carbon precursor obtained in step (2) is added to the template solution, the mass ratio of the polystyrene organic template microspheres to the composite porous carbon precursor is 1:1.5, the mixture is stirred for 10 minutes and then allowed to stand for 1 hour, so that the composite porous carbon precursor is loaded on the surface of the polydopamine coating layer to obtain a reaction solution, and the reaction solution is filtered, washed and dried to obtain composite precursor particles;

[0235] The composite precursor particles are heated to 700°C at a heating rate of 5°C / min and kept warm for 1 hour. After the heat preservation is completed, the composite carbide is cooled to room temperature with the furnace to complete high-temperature carbonization and obtain a composite carbide; subsequently, the composite carbide is immersed in a 15wt% hydrofluoric acid solution, and after immersion for 10 hours, it is filtered, washed and dried to obtain a primary porous carbon material, which consists of a carbon shell and nitrogen-phosphorus co-doped porous carbon microspheres loaded on the surface of the carbon shell;

[0236] (4) uniformly mixing the primary porous carbon material obtained in step (3) with potassium carbonate in a mass ratio of 1:2 and fully grinding to obtain an activated mixture; spreading the activated mixture evenly in a porcelain boat, placing the porcelain boat in a horizontal tube furnace, and pyrolyzing and activating the activated mixture under a nitrogen atmosphere. The pyrolysis and activation process includes:

[0237] First, the activated mixture was heated to 300°C at a heating rate of 3°C / min and kept warm for 30 minutes; then, the activated mixture was heated to 600°C at a heating rate of 5°C / min and kept warm for 1 hour; finally, the activated mixture was heated to 800°C at a heating rate of 8°C / min and kept warm for 2 hours. After the insulation was completed, it was cooled to room temperature with the furnace to complete the pyrolysis activation and obtain the activated product;

[0238] After the pyrolysis activation is completed, the activated product is washed with a 1.5 mol / L hydrochloric acid solution, and then the activated product is repeatedly rinsed with deionized water until it is neutral, thereby obtaining the porous carbon material.

[0239] Comparative Example 1

[0240] This comparative example provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. The difference from Example 1 is that in step (1), the mass ratio of halloysite to lignin in the precursor solution is adjusted to 1:1.1, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0241] Comparative Example 2

[0242] This comparative example provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. The difference from Example 1 is that in step (1), the mass ratio of halloysite to lignin in the precursor solution is adjusted to 1:1.5, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0243] Comparative Example 3

[0244] This comparative example provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. The difference from Example 1 is that in step (2), the mass ratio of organic template microspheres to dopamine in the dopamine solution is adjusted to 1:3, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0245] Comparative Example 4

[0246] This comparative example provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. The difference from Example 1 is that in step (2), the mass ratio of organic template microspheres to dopamine in the dopamine solution is adjusted to 1:6, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0247] Comparative Example 5

[0248] This comparative example provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. The difference from Example 1 is that in step (3), the holding time of high-temperature carbonization is adjusted to 0.5 h, and the other process parameters and operation steps are exactly the same as those in Example 1.

[0249] Comparative Example 6

[0250] This comparative example provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. The difference from Example 1 is that in step (3), the insulation time of high-temperature carbonization is adjusted to 3.5 h, and the other process parameters and operation steps are exactly the same as those in Example 1.

[0251] Comparative Example 7

[0252] This comparative example provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. The difference from Example 1 is that in step (4), the mass ratio of the primary porous carbon material to potassium carbonate is adjusted to 1:0.5, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0253] Comparative Example 8

[0254] This comparative example provides a method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin. The difference from Example 1 is that in step (4), the mass ratio of the primary porous carbon material to potassium carbonate is adjusted to 1:2.5, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0255] The electrochemical properties of the porous carbon materials prepared in Example 1 and Comparative Examples 1-4 were tested, and the specific test steps were as follows:

[0256] (1) Preparation of electrodes

[0257] The porous carbon material, carbon black and polytetrafluoroethylene prepared in Example 1 and Comparative Examples 1-4 were placed in a mortar at a mass ratio of 8:1:1, ground and mixed to obtain an active slurry, and the active slurry was coated on a rectangular titanium mesh with a size of 1×2 cm, placed in a vacuum drying oven at 60° C. for 12 h, and then pressed at a pressure of 10 MPa to obtain a working electrode; to ensure complete penetration of the electrolyte, the working electrode was immersed in the electrolyte for more than 12 h before the electrochemical test;

[0258] (2) Electrochemical testing

[0259] The prepared electrode material was subjected to cyclic voltammetry test, constant current charge-discharge test and cycle stability test in 1 mol / L H2SO4 electrolyte using CHI660E electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd.

[0260] In the cyclic voltammetry test, within a given voltage range, by controlling the change in voltage, a curve graph of current versus voltage is obtained. The voltage test range used during the test is -0.1~0.9V, and the scan rate is 50mV / s. After the test, the following is obtained: Fig.10 The cyclic voltammetry curves shown in the figure show that the cyclic voltammetry curves of all working electrodes are in a rectangular shape, which indicates that the double-layer capacitance characteristics are more prominent in the electrode material. In addition, the presence of redox peaks can be observed in the figure, which is the pseudocapacitance effect caused by nitrogen and phosphorus atom doping. The area enclosed by the working electrode made of the porous carbon material provided in Example 1 is significantly larger than the area enclosed by Comparative Examples 1-4, indicating that its specific capacitance is optimal. This is because the porous carbon material prepared in Example 1 has a higher specific surface area and a larger number of micropores, and nitrogen and phosphorus atoms also improve its performance.

[0261] The constant current charge and discharge test records the curve of voltage change over time at a given current density. The voltage test range used in the test is -0.1~0.9V and the current density is 0.5A / g. After the test, the following is obtained: Fig.11 The constant current charge-discharge curves shown in the figure show that the constant current charge-discharge curves of all working electrodes are symmetrical isosceles triangles, which proves their good electrochemical reversibility. In addition, the triangles of the constant current charge-discharge curves are deformed to a certain extent, which is the pseudocapacitance caused by nitrogen and phosphorus heteroatom doping. The specific capacitance and energy density of the working electrode at a current density of 0.5A / g are calculated through the constant current charge-discharge curves.

[0262] The specific capacitance of the working electrode was calculated using the following formula:

[0263] ;

[0264] Where C is the specific capacitance of the working electrode (F / g), I is the discharge current (A), ∆t is the discharge time (s), ∆V is the potential window (V), and m is the mass of the active slurry on the working electrode (g).

[0265] The energy density of the working electrode was calculated using the following formula:

[0266]

[0267] Where E is the energy density (Wh / kg), C is the specific capacitance of the working electrode (F / g), and ∆V is the potential window (V).

[0268] Long cycle life and stable performance are obvious advantages of supercapacitors in practical applications. The present invention adopts a blue battery test system to charge and discharge the capacitor 10,000 times at a constant current density of 10A / g, and calculates the capacitance retention rate (%) of the supercapacitor.

[0269] The electrochemical properties of the porous carbon materials prepared in Examples 1-5 and Comparative Examples 1-8 were tested according to the above test method, and the specific capacitance, energy density and capacitance retention rate of the working electrode were calculated. The test results are shown in Table 1.

[0270] Table 1 Electrochemical performance test results of porous carbon materials prepared in Examples 1-5 and Comparative Examples 1-8

[0271]

[0272] It can be seen from the data in Table 1 that the specific capacitance, energy density and capacitance retention rate of the porous carbon materials prepared in Examples 1-5 of the present invention are higher than those in Comparative Examples 1-8, which indicates that the porous carbon materials prepared by the preparation method provided by the present invention meet the requirements of supercapacitors for the electrochemical properties of battery materials.

[0273] It can be seen from the test data of Example 1, Comparative Example 1 and Comparative Example 2 that the specific capacitance, energy density and capacitance retention rate of the porous carbon materials prepared in Comparative Example 1 and Comparative Example 2 are lower than those in Example 1. This is because the amount of lignin added in Comparative Example 1 is too high and the amount of halloysite added is relatively low, while the amount of lignin added in Comparative Example 2 is too low and the amount of halloysite added is relatively high, which affects the pore structure of the porous carbon microspheres formed after high-temperature carbonization, and ultimately leads to a decrease in the electrochemical properties of the porous carbon material.

[0274] It can be seen from the test data of Example 1, Comparative Example 3 and Comparative Example 4 that the specific capacitance, energy density and capacitance retention rate of the porous carbon materials prepared in Comparative Example 3 and Comparative Example 4 are lower than those in Example 1. This is because the amount of dopamine added in Comparative Example 3 is too low, while the amount of dopamine added in Comparative Example 4 is too high, which affects the thickness of the carbon shell skeleton formed after high-temperature carbonization, resulting in the destruction of the pore structure of the porous carbon material, and ultimately leading to a decrease in the electrochemical performance of the porous carbon material.

[0275] It can be seen from the test data of Example 1, Comparative Example 5 and Comparative Example 6 that the specific capacitance, energy density and capacitance retention rate of the porous carbon materials prepared in Comparative Example 5 and Comparative Example 6 are lower than those in Example 1. This is because the holding time of high-temperature carbonization in Comparative Example 5 is too short, while the holding time of high-temperature carbonization in Comparative Example 6 is too long, which affects the morphology of the carbon shell skeleton and the porous carbon microspheres, resulting in the destruction of the pore structure of the porous carbon material, and ultimately leading to a decrease in the electrochemical performance of the porous carbon material.

[0276] It can be seen from the test data of Example 1, Comparative Example 7 and Comparative Example 8 that the specific capacitance, energy density and capacitance retention rate of the porous carbon materials prepared in Comparative Example 7 and Comparative Example 8 are lower than those in Example 1. This is because the amount of potassium carbonate added in Comparative Example 7 is too low, while the amount of potassium carbonate added in Comparative Example 8 is too high, which affects the activation effect of the primary porous carbon material, resulting in a decrease in the pore volume of the porous carbon material, and ultimately a decrease in the electrochemical performance of the porous carbon material.

[0277] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin, characterized in that: The method comprises: (I) dispersing lignin in deionized water to obtain a lignin solution, dropping an acetic acid solution into the lignin solution to adjust the pH value thereof, then sequentially adding chitosan and sodium dihydrogen phosphate into the lignin solution, mixing and stirring to obtain a precursor solution; adding halloysite to the precursor solution to obtain a suspension, placing the suspension in a negative pressure environment and then centrifuging at high speed, washing and freeze-drying the precipitate after centrifugation to obtain a porous carbon precursor; (II) dissolving hexadecyltrimethylammonium bromide in anhydrous ethanol to obtain a dispersed solution, adding an aqueous ammonia solution and the porous carbon precursor obtained in step (I) to the dispersed solution, mixing, stirring and ultrasonically dispersing to obtain a reaction precursor solution; preparing a hydrolyzate containing tetraethyl orthosilicate, adding the reaction precursor solution to the hydrolyzate while stirring to obtain a composite precursor sol, allowing the composite precursor sol to stand and age under a constant temperature environment to obtain a composite precursor gel; freeze-drying the composite precursor gel to obtain a composite porous carbon precursor; (III) adding organic template microspheres to a dopamine solution, mixing and stirring, and then standing to obtain a template solution; then, adding the composite porous carbon precursor obtained in step (II) to the template solution, mixing and stirring, and then standing to obtain a reaction solution, filtering, washing and drying the reaction solution to obtain composite precursor particles; high-temperature carbonizing the composite precursor particles to obtain a composite carbide; then, immersing the composite carbide in a hydrofluoric acid solution, filtering, washing and drying to obtain a primary porous carbon material; (IV) Evenly mixing the primary porous carbon material obtained in step (III) with potassium carbonate and grinding them thoroughly to obtain an activated mixture; spreading the activated mixture evenly in a porcelain boat, placing the porcelain boat in a horizontal tube furnace, and pyrolyzing and activating the activated mixture under a nitrogen atmosphere to obtain an activated product, and washing the activated product to obtain the porous carbon material.

2. The method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin according to claim 1, characterized in that: In step (I), the lignin is prepared by the following method: The biomass raw material is crushed, sieved and frozen with liquid nitrogen in sequence to obtain biomass powder; the biomass powder is dispersed in an ethanol aqueous solution to form a biomass dispersion liquid, the biomass dispersion liquid is preheated by microwave, and then the biomass dispersion liquid is simultaneously subjected to ultrasonic treatment and microwave treatment, and after the treatment, extraction and filtration are performed, a hydrochloric acid solution is added to the filtrate to adjust its pH value, and a precipitate is taken out after centrifugal separation and dried to obtain lignin; The biomass raw material includes any one of corn straw, rice straw, wheat straw, wood chips, sawdust, fruit shells or fruit cores, or a combination of at least two thereof; The mesh size of the sieve used in the sieving is 100 to 200 meshes; The operation process of the liquid nitrogen freezing is as follows: immersing the sieved raw material powder in liquid nitrogen, taking it out after immersing it for a period of time, immersing it in liquid nitrogen again, and repeating it multiple times; The raw material powder is immersed in liquid nitrogen for 3 to 5 minutes each time, and the raw material powder is immersed in liquid nitrogen 5 to 8 times; The mass ratio of the biomass powder to the ethanol aqueous solution is (0.1-0.3):1; The volume fraction of ethanol in the ethanol aqueous solution is 30-40%; The microwave power of the microwave preheating of the biomass dispersion is 700-800W; The microwave frequency of the microwave preheating of the biomass dispersion is 500-600 MHz; The microwave preheating treatment time of the biomass dispersion is 5 to 8 minutes; The ultrasonic power of the ultrasonic treatment of the biomass dispersion is 1000-2000W; The ultrasonic frequency of the ultrasonic treatment of the biomass dispersion is 0.5-1.5 MHz; The microwave power of the microwave treatment of the biomass dispersion is 2000-3000W; The microwave frequency of the microwave treatment of the biomass dispersion is 1000-1500 MHz; The treatment time of the ultrasonic treatment and microwave treatment of the biomass dispersion is 10 to 20 minutes; The extraction time is 50 to 60 minutes; The extraction temperature is 60-80°C; The solid-liquid ratio of the leaching is 1g:(10-20)mL; The organic solvent used in the leaching is any one of ethylene glycol, 1,4-butanediol, acetone or methanol, or a combination of at least two thereof; The concentration of the hydrochloric acid solution is 1.5-2.5 mol / L; A hydrochloric acid solution was added to the filtrate to adjust the pH value of the filtrate to 3-5.

3. The method for preparing porous carbon material by microwave-assisted extraction of biomass lignin according to claim 1, characterized in that: In step (I), the mass ratio of the lignin to the deionized water is 1:(20-30); The mass fraction of the acetic acid solution is 8-12wt%; Adding acetic acid solution dropwise to the lignin solution to adjust the pH value of the lignin solution to 5-6; The mass ratio of lignin, chitosan and sodium dihydrogen phosphate in the lignin solution is 1:(0.4-0.5):(0.6-0.7).

4. The method for preparing porous carbon material by microwave-assisted extraction of biomass lignin according to claim 1, characterized in that: In step (I), the mass ratio of the halloysite to the lignin in the precursor solution is 1:(1.2-1.4); After adding halloysite to the precursor solution, ultrasonic dispersion is performed to obtain the suspension, wherein the ultrasonic power of the ultrasonic dispersion is 200-300W, and the ultrasonic time of the ultrasonic dispersion is 30-40min; The pressure of the negative pressure environment is -0.5~-0.7MPa; The suspension is allowed to stand for 1.5 to 2.5 hours under the negative pressure environment; The speed of the high-speed centrifugation is 2000-3000 r / min; The high-speed centrifugation time is 1 to 2 hours; The freeze drying temperature is -40 to -50°C; The freeze-drying time is 24 to 36 hours.

5. The method for preparing porous carbon material by microwave-assisted extraction of biomass lignin according to claim 1, characterized in that: In step (II), the mass fraction of hexadecyltrimethylammonium bromide in the dispersed solution is 3-5wt%; The ratio of hexadecyltrimethylammonium bromide, the aqueous ammonia solution and the porous carbon precursor in the dispersed solution is (5-6) g: (30-50) mL: 1 g; The concentration of the ammonia solution is 22-25 wt %; The ultrasonic power after adding the ammonia solution and the porous carbon precursor to the dispersed solution is 400-500W; The ultrasonic time after adding the ammonia solution and the porous carbon precursor to the dispersed solution is 20 to 30 minutes; The hydrolyzate containing ethyl orthosilicate is prepared by the following method: Mixing and stirring tetraethyl orthosilicate, ethanol and deionized water to obtain a tetraethyl orthosilicate solution, adding a nitric acid solution dropwise to the tetraethyl orthosilicate solution to adjust the pH value thereof, and then stirring the tetraethyl orthosilicate solution to obtain a hydrolyzate; The volume ratio of the tetraethyl orthosilicate, ethanol and deionized water is 1:(1.6-1.7):(0.2-0.3); The concentration of the nitric acid solution is 1-2 mol / L; Adding nitric acid solution dropwise to the tetraethyl orthosilicate solution to adjust the pH value of the tetraethyl orthosilicate solution to 4-5; The stirring time of the ethyl orthosilicate solution is 5 to 6 hours.

6. The method for preparing porous carbon material by microwave-assisted extraction of biomass lignin according to claim 1, characterized in that: In step (II), the hydrolyzate and the reaction precursor solution are mixed according to a volume ratio of the tetraethyl orthosilicate to the ammonia solution of 1:(3-5); The temperature of the constant temperature environment is 40-45°C; The composite precursor sol is placed in a constant temperature environment for 3 to 5 hours; The freeze-drying temperature of the composite precursor gel is -40 to -50°C; The freeze-drying time of the composite precursor gel is 24 to 36 hours.

7. The method for preparing porous carbon material by microwave-assisted extraction of biomass lignin according to claim 1, characterized in that: In step (III), the dopamine solution is prepared by the following method: dissolving dopamine in Tris-HCl buffer to obtain a dopamine solution; The concentration of dopamine in the dopamine solution is 5-8 g / L; The pH value of the dopamine solution is 8-9; The particle size of the organic template microspheres is 4-5 μm; The material of the organic template microspheres is polystyrene; The mass ratio of the organic template microspheres to the dopamine in the dopamine solution is 1:(4-5); The organic template microspheres are added to the dopamine solution and mixed and stirred for 30 to 40 minutes, and then allowed to stand for 8 to 10 hours; The mass ratio of the organic template microspheres to the composite porous carbon precursor in the template solution is 1:(1.3-1.5); The composite porous carbon precursor is added to the template solution, mixed and stirred for 5 to 10 minutes, and then allowed to stand for 1 to 2 hours.

8. The method for preparing porous carbon material by microwave-assisted extraction of biomass lignin according to claim 1, characterized in that: In step (III), the heating rate of the high temperature carbonization is 3-5°C / min; The heating temperature of the high temperature carbonization is 600-700°C; The high temperature carbonization holding time is 1 to 3 hours; The concentration of the hydrofluoric acid solution is 5-15wt%; The composite carbide is immersed in the hydrofluoric acid solution for 10 to 20 hours.

9. The method for preparing porous carbon material by microwave-assisted extraction of biomass lignin according to claim 1, characterized in that: In step (IV), the mass ratio of the primary porous carbon material to the potassium carbonate is 1:(1-2); The pyrolysis activation process comprises: First, the activation mixture is heated to a first temperature at a first heating rate and kept warm, then, the activation mixture is continued to be heated to a second temperature at a second heating rate and kept warm, and finally, the activation mixture is heated to a third temperature at a third heating rate and kept warm, and after the insulation is completed, the mixture is cooled to room temperature with the furnace to complete the pyrolysis activation and obtain the activation product; The first heating rate is 2-3°C / min; The first temperature is 200-300° C.; The activated mixture is kept at the first temperature for 30 to 40 minutes; The second heating rate is 4-5°C / min; The second temperature is 500-600° C.; The activated mixture is kept at the second temperature for 1 to 2 hours; The third heating rate is 6-8°C / min; The third temperature is 700-800° C. The activated mixture is kept at the third temperature for 2 to 3 hours; The washing process comprises: The activated product is washed with a hydrochloric acid solution, and then repeatedly rinsed with deionized water until the activated product is neutral; The concentration of the hydrochloric acid solution is 0.5-1.5 mol / L.

10. An application of the method for preparing porous carbon materials by microwave-assisted extraction of biomass lignin according to any one of claims 1 to 9, characterized in that: The porous carbon material prepared by the method is used for supercapacitors.

Citation Information

Patent Citations

  • Lignin porous carbon with even pore channels and preparation method thereof and application in lithium ion battery anode material

    CN108751160A

  • Preparation method of lignin hierarchical porous carbon material with endellite as template

    CN105664848A

  • Lignin-based carbon nano tube taking halloysite as template and preparation method of lignin-based carbon nano tube

    CN114956054A